Silicon-oxygen material, negative electrode material and manufacturing method thereof, and lithium-ion battery
Silicon oxide materials with high sphericity and reducing metal compounds address the volumetric expansion issue in SiOx negative electrodes, enhancing cycling performance and efficiency in lithium-ion batteries.
Patent Information
- Application Number
- JP2023528208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-25
- Filing Date
- 2022-06-23
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2042-06-23
AI Technical Summary
SiOx (0
The development of silicon oxide materials with a Wadell sphericity greater than 0.92, combined with reducing metals or compounds, which uniformly expand and contract, reducing electrolyte penetration and minimizing SEI film formation, thereby enhancing structural stability and cycling performance.
The silicon oxide materials with high sphericity and reducing metal compounds improve cycling performance by reducing volumetric expansion, irreversible capacity loss, and maintaining structural integrity, resulting in higher initial coulombic efficiency and extended cycle life.
Smart Images

Figure 0007606198000021 
Figure 0007606198000022 
Figure 0007606198000023
Abstract
Description
Detailed Description of the Invention
[0001] (Related Application) This application claims the priority of a Chinese patent application with the application number 2021107119628 and the invention title "Silicon Oxide, Anode Material, Manufacturing Method and Application", which was filed with the Chinese Patent Office on June 25, 2021, and all of its contents are incorporated herein by reference.
Technical Field
[0002] This application relates to the technical field of anode materials, specifically, to silicon oxygen materials, anode materials and their manufacturing methods, and lithium-ion batteries.
Background Art
[0003] SiOx (0 < x < 2) anode materials are currently the most promising lithium-ion battery anode materials, which overcome the disadvantages of low specific capacity of graphite, high lithium storage voltage platform of silicon single crystal, and relatively poor cycle and rate performance, while having good safety and a wide range of raw material sources. However, SiOx anode materials have a volume expansion rate of about 200% during the cycling process, and how to reduce the volume expansion of SiOx anode materials has become the focus of research in the industry.
Summary of the Invention
Problems to be Solved by the Invention
[0004] In view of this, this application provides a silicon oxygen material, an anode material and its manufacturing method, and a lithium-ion battery, which can improve the first Coulomb efficiency of the silicon anode material while reducing the manufacturing cost.
Means for Solving the Problems
[0005] In a first aspect, the present application provides a silicon-oxygen material, the silicon-oxygen material includes a silicon oxide, the chemical formula of the silicon oxide is SiOx (0 < x < 2), the silicon-oxygen material is a primary particle, and the Wadell sphericity of the primary particle is greater than 0.92.
[0006] The silicon-oxygen material related to the present application includes a silicon oxide, and the silicon oxide is a primary particle of a spherical silicon oxide with a Wadell sphericity greater than 0.92. Since the spherical particles have isotropic characteristics, they uniformly contract and expand outward along the radial direction during the cycling process, can withstand isotropic stress and maintain the stability of the structure, and the "weak points" of stress caused by shape non-uniformity do not appear. Therefore, the possibility of the electrolyte penetrating into the material due to the collapse of the particle structure and the rupture of the SEI film is significantly reduced, and the continuous penetration of the electrolyte into the material to generate a new SEI film is effectively avoided. The repeated crushing and generation of the SEI film are avoided, the volume expansion of the material is reduced, and the cycle performance of the material is improved. Also, among particles of the same volume, the specific surface area of spherical particles is the smallest, and since the SEI film generated during the cycling process is the least, the irreversible charge capacity is effectively reduced, and the irreversible capacity loss during the cycling process can be further reduced.
[0007] In some embodiments, the silicon-oxygen material further includes at least one of a reducing metal and a reducing metal compound.
[0008] The silicon-oxygen material according to the present invention includes silicon oxide, a reducing metal and / or a reducing metal compound, in which Si, O and the reducing metal are uniformly distributed in the primary particles of the silicon oxide, and the silicon-oxygen material is a spherical primary particle with a Wadell sphericity of greater than 0.92, and since the spherical particles have isotropic characteristics, they contract and expand uniformly outward along the radial direction during the circulation process, and can maintain the stability of the structure under isotropic stress, and there is no "weak point" of stress due to the uneven shape, so that the possibility of electrolyte penetrating into the material due to collapse of the particle structure and rupture of the SEI film is greatly reduced, and the electrolyte penetrating into the material and continuing to generate a new SEI film is effectively avoided, and the repeated fracture and generation of the SEI film is avoided, the volume expansion of the material is reduced, and the cycle performance of the material is improved. In addition, the specific surface area of the spherical particles is the smallest among particles of the same volume, and the SEI film generated during the circulation process is the smallest, so that the irreversible charge capacity is effectively reduced, and the irreversible capacity loss during the circulation process can be further reduced.
[0009] In some possible embodiments, the reducing metal comprises at least one of an alkali metal, an alkaline earth metal, and a transition metal.
[0010] In some possible embodiments, the reducing metal element includes at least one of Li, K, Mg, Al, Ca, Zn, Na, and Ti.
[0011] In some possible embodiments, the mass content of oxygen element in the silicon-oxygen material is 10% to 50%.
[0012] In some possible embodiments, the mass content of the reducing metal element in the silicon-oxygen material is 0.5% to 50%.
[0013] In some possible embodiments, in an element distribution map obtained by scanning an SEM cut surface of a primary particle of the silicon-oxygen material with an X-ray, the distribution surfaces of Si, O and reducing metal elements are in a uniformly dispersed state.
[0014] In some possible embodiments, the reducible metal compound comprises at least one of a reducible metal oxide, a reducible metal silicide, and a reducible metal silicate.
[0015] In some possible embodiments, the reducible metal compound comprises a reducible metal silicate, and the reducible metal silicate is uniformly distributed within the primary particles.
[0016] In some possible embodiments, the reducible metal compound comprises a reducible metal silicate, and the mass content of the silicate in the silicon-oxygen material is 10% to 80%.
[0017] In some possible embodiments, the reducible metal compound comprises a reducible metal silicate, and the silicate comprises lithium silicate.
[0018] In some possible embodiments, the reducible metal compound comprises a silicate of a reducible metal, the silicate comprising a lithium silicate, the lithium silicate comprising at least one of Li2SiO3, Li4SiO4, Li2Si2O5, and Li2Si3O7.
[0019] In some possible embodiments, the reducible metal compound comprises a silicate of a reducible metal, the silicate comprises a lithium silicate, and the lithium silicate is Li2Si2O5.
[0020] In some possible embodiments, the reducible metal compound comprises a silicate of a reducible metal, the silicate comprising crystalline Li2Si2O5, the grain size of Li2Si2O5 being less than 20 nm.
[0021] In some possible embodiments, the reducible metal compound comprises a silicate of a reducible metal, the silicate comprises crystalline Li2Si2O5, and the mass content of Li2Si2O5 in the silicon-oxygen material is between 20% and 80%.
[0022] In some possible embodiments, the reducible metal compound comprises a silicate of a reducible metal, the silicate comprises lithium silicate, and the molar ratio of Si to Li in the silicon-oxygen material is (1-50):1.
[0023] In some possible embodiments, the Wadell sphericity of the primary particles is greater than 0.95.
[0024] In some possible embodiments, the Si crystallite size in the silicon oxygen material is less than or equal to 20 nm.
[0025] In some possible embodiments, the Si crystallite size in the silicon oxygen material is 10 nm or less.
[0026] In some possible embodiments, the average grain size D of the silicon-oxygen material 50 D 50 Meets ≦50μm.
[0027] In some possible embodiments, the particle size distribution of the silicon oxygen material is greater than or equal to 3 μm. <D 50 <10μm, 2μm≦D 10 ≦5μm and 0.8≦(D 90 -D 10 ) / D 50 ≦1.2.
[0028] In some possible embodiments, the specific surface area of the silicon-oxygen material is greater than 10 m 2 / g.
[0029] In some possible embodiments, the silicon oxygen material further comprises a non-metallic doping element.
[0030] In a second aspect, the present application provides an anode material, the anode material comprising the silicon-oxygen material described above.
[0031] In some possible embodiments, the anode material further comprises a carbon layer coated on the surface of the silicon oxygen material.
[0032] In the above solution, the carbon layer is formed on the surface of the primary particles of silicon-oxygen material, which can effectively prevent the primary particles from bursting and pulverizing during charging and discharging cycles, reduce the volume expansion of the material, and ensure the structural stability of the primary particles inside the negative electrode material. After being coated with the carbon layer, it has higher electrical conductivity and stability, effectively avoids the internal voids of the carbon filling material, and improves the initial efficiency of the material, so that the negative electrode material can exhibit characteristics such as high capacity, long cycle life, high magnification performance and low expansion.
[0033] In some possible embodiments, the difference between the maximum and minimum thicknesses of the carbon layer is less than the minimum thickness.
[0034] In some possible embodiments, the carbon layer has a thickness of 10 nm to 500 nm.
[0035] In some possible embodiments, the negative electrode material D 50 D 50 Meets the requirement of ≦100μm.
[0036] In some possible embodiments, the negative electrode material further comprises a metal compound, the metal compound comprising at least one of a metal oxide, a metal silicide, and a metal silicate.
[0037] In some possible embodiments, the anode material further comprises a carbon material, the silicon oxygen material is dispersed in the carbon material, the anode material is a spherical particle, and the Wadell sphericity of the anode material is greater than 0.3.
[0038] In some possible embodiments, the negative electrode material has a Wadell sphericity of greater than 0.5.
[0039] In some possible embodiments, the negative electrode material has a Wadell sphericity of greater than 0.92.
[0040] In some possible embodiments, in the silicon-oxygen material, the mass of the oxygen element accounts for 0% to 67% (but not including 0%) of the sum of the masses of the silicon element and the oxygen element.
[0041] In some possible embodiments, the negative electrode material D 50 D 50 Meets ≦40μm.
[0042] In some possible embodiments, the porosity of the negative electrode material is less than 20%.
[0043] In some possible embodiments, the silicon-oxygen material comprises 40% to 95% by mass of the negative electrode material.
[0044] In some possible embodiments, the anode material further comprises a carbon material, the silicon oxygen material being dispersed in the carbon material, and the carbon material comprising amorphous carbon.
[0045] In some possible embodiments, the negative electrode material further comprises graphite.
[0046] In some possible embodiments, the negative electrode material further comprises graphite, the graphite comprising at least one of natural graphite, synthetic graphite, and mesocarbon microbeads.
[0047] In some feasible embodiments, the negative electrode material further comprises graphite, and when a total mass of the negative electrode material is 100%, a mass fraction of the graphite is 0% to 40%, a mass fraction of the silicon-oxygen material is 40% to 95%, and a mass fraction of the carbon material is 5% to 60%.
[0048] In some possible embodiments, the anode material further comprises a carbon material, the carbon material being grown in situ to form on the surface of the silicon-oxygen material, and the carbon material having a graphene structure.
[0049] In some possible embodiments, the negative electrode material has a carbon characteristic peak D, a carbon characteristic peak G, a silicon characteristic peak A, and a graphene characteristic peak B in a Raman spectrum.
[0050] In some possible embodiments, the peak intensity I of the silicon characteristic peak A A and the peak intensity I of the graphene characteristic peak B B Comparison with I A / I B is 0.1 to 50, and the peak intensity I of the carbon characteristic peak D D and the peak intensity I of the carbon characteristic peak G G Comparison with I D / I G is 0.5 to 2.0, and the peak intensity I of the graphene characteristic peak B is B and the peak intensity I of the carbon characteristic peak D D Comparison with I B / I D is between 0 and 1.
[0051] In some possible embodiments, the negative electrode material further comprises a carbon material, the silicon oxygen material is dispersed in the carbon material, the negative electrode material is a secondary particle, and the Wadell sphericity of the negative electrode material is greater than 0.91.
[0052] In the above-mentioned solution, the negative electrode material is a secondary particle, and the primary particles of the silicon-oxygen material are dispersed in the carbon material, and the carbon layer in the secondary particle not only covers the surface of the silicon-oxygen material particle, but also connects the silicon-oxygen material to form the secondary particle, so as to have excellent electrochemical performance. The porous structure inside the secondary particle can absorb a part of the volume expansion and synergize with the improvement of the cycling performance of the material. And the carbon filled between the primary particles can provide good electrical contact between the particles, reducing the direct contact between the electrolyte and the active material, and avoiding the cycle deterioration caused by the loss of electrical contact between the active material when the particles are powdered. It achieves excellent electrochemical performance in synergy with the stability of the spherical structure.
[0053] In some possible embodiments, the silicon oxygen material is a primary particle of silicon oxide.
[0054] In some possible embodiments, the volume of the silicon oxide powder having a grain size of 1.0 μm or less accounts for 15% or less of the total silicon oxide volume.
[0055] In some possible embodiments, the grain size of the silicon oxide is D 90 <25.0μm, D 10 >0.5μm and 1μm≦D 50 Meets ≦10μm.
[0056] In some possible embodiments, the silicon oxide has a Si crystallite size of 1.0 nm to 20 nm.
[0057] In some possible embodiments, the specific surface area of the negative electrode material is less than 0.5 m 2 / g~50m 2 / g.
[0058] In some possible embodiments, the tap density of the negative electrode material is less than or equal to 0.5 g / cm 3 ~5.0g / cm 3 It is.
[0059] In some possible embodiments, the particle size D of the negative electrode material 50 is the particle diameter D of the silicon oxide 50 It is 2 to 10 times that.
[0060] In some possible embodiments, the particle size of the negative electrode material is 6 μm≦D 90 ≦8μm, 4μm <D 50 <6μm and 2μm≦D 10 Meets ≦3μm.
[0061] In some possible embodiments, the mass content of carbon element in the negative electrode material is 2% to 20%.
[0062] In some possible embodiments, the porosity of the negative electrode material is between 1% and 50%.
[0063] In some possible embodiments, the anode material further comprises a coating layer overlying the silicon-oxygen material, the coating layer comprising a flexible polymer.
[0064] In the above solution, the coating layer is coated on the surface of the primary particles of the silicon-oxygen material, and the high-strength flexible polymer is coated on the surface of the silicon-oxygen material, which can more effectively suppress the expansion of the silicon-oxygen material, and the coated negative electrode material has high electrical conductivity, stable electrical conductivity, and excellent cycle expansion performance.
[0065] In some possible embodiments, the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer.
[0066] In some possible embodiments, the flexible polymer comprises at least one of polyolefins and their derivatives, polyvinyl alcohol and its derivatives, polyacrylic acid and its derivatives, polyamides and its derivatives, carboxymethylcellulose and its derivatives, and alginic acid and its derivatives.
[0067] In some possible embodiments, the flexible polymer has a weight average molecular weight of 2,000 to 1,000,000.
[0068] In some possible embodiments, the flexible polymer comprises thermally crosslinkable functional groups, the thermally crosslinkable functional groups comprising at least one of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond.
[0069] In some possible embodiments, the coating layer further comprises an electrically conductive material.
[0070] In some possible embodiments, the conductive material includes flake graphite and nano-carbon based materials.
[0071] In some possible embodiments, the flake graphite includes natural flake graphite and / or artificial flake graphite.
[0072] In some possible embodiments, the nano-carbon-based material comprises at least one of conductive graphite, graphene, carbon nanotubes, and carbon nanofibers.
[0073] In some possible embodiments, the coating layer further comprises a water-insoluble lithium silicate.
[0074] In some possible embodiments, the water-insoluble lithium silicate comprises at least one of Li2SiO3 and Li2Si2O5.
[0075] In some possible embodiments, the mass percentage of the flexible polymer is between 0 and 10% (but not including 0) when the total mass of the silicon-oxygen material is taken as 100%.
[0076] In some feasible embodiments, when the total mass of the silicon oxygen material is 100%, the mass percentage of the flaky graphite is 0 to 20% (excluding 0).
[0077] In some feasible embodiments, when the total mass of the silicon oxygen material is 100%, the mass percentage of the nano carbon-based material is 0 to 5% (excluding 0).
[0078] In some feasible embodiments, the flexible polymer includes polycarbonate.
[0079] In some feasible embodiments, the thickness of the coating layer is 10 nm to 5000 nm.
[0080] In some feasible embodiments, the mass ratio of the coating layer in the negative electrode material is 0% to 20% (excluding 0%).
[0081] In some feasible embodiments, the mass ratio of the coating layer in the negative electrode material is 2% to 10%.
[0082] The 3 In the aspect, the present application provides a method for manufacturing a negative electrode material. The manufacturing method includes the following steps. That is,
[0083] A step of conveying a raw material for manufacturing a silicon oxygen material into a plasma stream for reaction,
[0084] A step of cooling the product after the reaction to obtain a silicon oxygen material containing silicon oxide. The silicon oxygen material is primary particles, the chemical formula of the silicon oxide is SiOx (0 < x < 2), and the wadell sphericity of the primary particles is greater than 0.92.
[0085] In the above solution, the raw material enters the plasma flow and reacts at a high temperature, while generating silicon oxide droplets. The silicon oxide droplets are cooled and automatically become spherical under the action of surface tension, and then harden into spherical silicon oxide. Since the spherical silicon oxide particles can maintain structural stability during the circulation process, the material has a low expansion rate and excellent cycle performance.
[0086] No. 4 In an aspect, the present application provides a method for manufacturing a negative electrode material. The manufacturing method includes the following steps.
[0087] The raw material for manufacturing the silicon oxygen material is heat-treated and then cooled to obtain a silicon oxygen material containing silicon oxide. The chemical formula of the silicon oxide is SiOx (0 < x < 2), and the Wadell sphericity of the silicon oxygen material is greater than 0.92.
[0088] In the above solution, by heat-treating the raw material, silicon oxide droplets are generated at a high temperature. The silicon oxide droplets are cooled and automatically become spherical under the action of surface tension, and then harden into spherical silicon oxide. Since the spherical silicon oxide particles can maintain structural stability during the circulation process, the material has a low expansion rate and excellent cycle performance.
[0089] In some feasible embodiments, the step of heat-treating the raw material for manufacturing the silicon oxygen material includes performing a plasma reaction on the raw material for manufacturing the silicon oxygen material.
[0090] In some feasible embodiments, the step of heat-treating the raw material for manufacturing the silicon oxygen material includes transporting the raw material for manufacturing the silicon oxygen material into the plasma flow to perform a plasma reaction.
[0091] In some feasible embodiments, the raw material for manufacturing the silicon oxygen material is a mixture of Si, SiO y and SiO2, and SiO yand Si, and a mixture of Si and SiO2, <y<2である。
[0092] In some possible embodiments, the raw materials for producing the silicon-oxygen material include SiH4 and O2.
[0093] In some possible embodiments, the step of heat treating the raw material to produce the silicon-oxygen material includes transporting the raw material to produce the silicon-oxygen material into a plasma flow to carry out a plasma reaction, and the temperature in the plasma flow is 1400°C to 2400°C.
[0094] In some possible embodiments, the step of heat treating the raw material for producing the silicon-oxygen material includes transporting the raw material for producing the silicon-oxygen material into a plasma flow to perform a plasma reaction, and the supply rate of the silicon oxide raw material is 2.0 g / min to 80 g / min.
[0095] In some possible embodiments, the step of thermally treating the source material to produce the silicon-oxygen material comprises transporting the source material to produce silicon oxide into said plasma flow using a carrier gas to carry out the plasma reaction.
[0096] In some possible embodiments, the step of heat treating the raw material to produce the silicon-oxygen material includes transporting the raw material to produce silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas.
[0097] In some possible embodiments, the step of heat treating the raw material to produce the silicon-oxygen material includes transporting the raw material to produce silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas, the reducing gas including at least one of methane and hydrogen gas.
[0098] In some possible embodiments, the step of heat treating the raw material for producing a silicon-oxygen material includes: using a carrier gas to transport the raw material for producing silicon oxide into the plasma flow to carry out a plasma reaction; and introducing a reducing gas, wherein the molar ratio of the reducing gas to the silicon oxide is 0 to 0.25 (but does not include 0).
[0099] In some possible embodiments, the step of heat treating the raw material to produce a silicon-oxygen material includes carrying the raw material to produce silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas, the radial velocity of the reducing gas being 1 m 3 / h~10m 3 / h.
[0100] In some possible embodiments, the source material for producing the silicon oxygen material further comprises a reducing metal.
[0101] In some possible embodiments, the source for producing the silicon-oxygen material further comprises a reducing metal, the reducing metal comprising at least one of an alkali metal, an alkaline earth metal, and a transition metal.
[0102] In some possible embodiments, the source material for producing the silicon-oxygen material further comprises a reducing metal, the reducing metal comprising at least one of Li, K, Mg, Al, Ca, Zn, Na, and Ti.
[0103] In some possible embodiments, the raw material for producing the silicon-oxygen material further comprises a reducing metal, the reducing metal comprises Li, and the molar ratio of Si to Li in the raw material for producing the silicon oxide is (1 to 50):1.
[0104] In some possible embodiments, the raw material for producing the silicon-oxygen material further comprises a reducing metal, the reducing metal comprises Mg, and the molar ratio of Si to Mg in the raw material for producing the silicon oxide is (5-50):1.
[0105] In some possible embodiments, the method further comprises washing the heat-treated product with water and / or pickling, washing the washed product until neutral, and performing solid-liquid separation and drying.
[0106] In some possible embodiments, the step of heat treating the source material to produce the silicon-oxygen material comprises atomizing the molten silicon-oxygen material source material.
[0107] In some possible embodiments, the step of thermally treating the source material to produce the silicon-oxygen material comprises atomizing the molten source material of silicon-oxygen material with a pressurized gas.
[0108] In some possible embodiments, the step of heat treating the raw material to produce the silicon-oxygen material includes atomizing the molten silicon-oxygen material raw material with a pressurized gas, the pressurized gas being a protective gas, the protective gas including at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0109] In some possible embodiments, the step of heat treating the raw material for producing the silicon-oxygen material includes atomizing the molten silicon-oxygen material raw material with pressurized gas, and the pressure of the pressurized gas is between 0.2Mpa and 100Mpa.
[0110] In some possible embodiments, the cooling step comprises cooling the silicon oxide source droplets to a temperature of 100° C. or less.
[0111] In some possible embodiments, the cooling rate is between 1° C. / s and 100° C. / s.
[0112] In some possible embodiments, the cooling is cooling with a protective gas, and the protective gas includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0113] In some possible embodiments, the silicon oxide source is SiOz, 0 <z<2である。
[0114] In some possible embodiments, the silicon oxide source comprises at least one of SiO, a mixture of Si and SiO2, a mixture of Si and SiO2, and a mixture of SiO and SiO2.
[0115] In some possible embodiments, the step of heat-treating the raw material to produce the silicon-oxygen material includes heat-treating the raw material including the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform an atomization process.
[0116] In some possible embodiments, the step of heat-treating the raw material for producing the silicon-oxygen material includes heat-treating the raw material including the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform a mist treatment, and the organic carbon source includes at least one of sugars, esters, hydrocarbons, organic acids, and polymers.
[0117] In some possible embodiments, the step of heat treating the raw material for producing the silicon-oxygen material includes heat treating the raw material including the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform a mist treatment, and the organic carbon source is selected from the group consisting of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, citric acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, and the like. ,a The resin composition contains at least one of sphalt, furfural resin, epoxy resin, and phenolic resin.
[0118] In some possible embodiments, the step of heat-treating the raw material for manufacturing the silicon oxygen material includes heat-treating the raw material containing the silicon oxygen material and the organic carbon source to melt the organic carbon source and perform an atomization treatment, and the mass ratio of the organic carbon source to the silicon oxide is 5:(5-95).
[0119] In some possible embodiments, the step of heat-treating the raw material for manufacturing the silicon oxygen material includes heat-treating the raw material containing the silicon oxygen material and the organic carbon source to melt the organic carbon source and perform an atomization treatment, and the raw material containing the silicon oxygen material and the organic carbon source further includes graphite.
[0120] In some possible embodiments, the method further includes performing a carbonization treatment on the cooled product to obtain a negative electrode material.
[0121] In some possible embodiments, the method further includes performing a carbonization treatment on the cooled product to obtain a negative electrode material, and the temperature of the carbonization treatment is 600°C - 1000°C.
[0122] In some possible embodiments, the manufacturing method further includes conveying a carbon source gas and a silicon oxygen material into a plasma stream for secondary granulation, and cooling to obtain a negative electrode material containing a silicon oxide and a carbon material, the negative electrode material is secondary particles, the chemical formula of the silicon oxide is SiOx(0 < x < 2), and the Wadell sphericity of the negative electrode material is greater than 0.91.
[0123] In some possible embodiments, the silicon oxygen material is primary particles of a silicon oxide.
[0124] In some possible embodiments, among the silicon oxides, the volume of the powder with a particle size of 1.0 μm or less accounts for 15% or less of the volume of all the silicon oxides.
[0125] In some possible embodiments, the grain size of the silicon oxide is D 90 <25.0μm, D 10 >0.5μm and 1μm≦D 50 Meets ≦10μm.
[0126] In some possible embodiments, the silicon oxide has a Si crystallite size of 1.0 nm to 20 nm.
[0127] In some possible embodiments, the carbon source gas comprises hydrocarbons.
[0128] In some possible embodiments, the carbon source gas comprises at least one of methane, acetylene, ethylene, ethane, propane, propene, propyne, acetone, and benzene.
[0129] In some possible embodiments, the volume ratio of the carrier gas to the carbon source gas is 10:(0.5-10).
[0130] In some possible embodiments, the step of conveying the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further comprises adding a carbonaceous binder into the plasma flow.
[0131] In some possible embodiments, the step of conveying the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further comprises adding a carbonaceous adhesive into the plasma flow, the carbonaceous adhesive comprising at least one of sugars, esters, hydrocarbons, organic acids, and polymers.
[0132] In some possible embodiments, the step of conveying the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous adhesive into the plasma flow, the carbonaceous adhesive comprising at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin.
[0133] In some possible embodiments, the step of conveying the carbon source gas and the silicon-oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous adhesive into the plasma flow, and the mass ratio of the carbonaceous adhesive to the silicon oxide is 5:95 to 50:50.
[0134] In some possible embodiments, the particle size D of the negative electrode material 50 is the particle diameter D of the silicon oxide 50 It is 2 to 10 times that.
[0135] In some possible embodiments, the particle size of the negative electrode material is 20 μm≦D 90 ≦50μm, 5μm <D 50 <20μm and 2μm≦D 10 Meets ≦5μm.
[0136] In some possible embodiments, the mass content of carbon element in the negative electrode material is 2% to 20%.
[0137] In some possible embodiments, the porosity of the negative electrode material is between 1% and 50%.
[0138] In some possible embodiments, the specific surface area of the negative electrode material is less than 0.5 m 2 / g~50m 2 / g.
[0139] In some possible embodiments, the tap density of the negative electrode material is less than or equal to 0.5 g / cm 3 ~5.0g / cm 3 It is.
[0140] In some possible embodiments, the method further comprises performing a carbon coating process on the silicon-oxygen material to obtain a negative electrode material.
[0141] In some possible embodiments, the method further comprises performing a carbon coating process on the silicon-oxygen material, the carbon coating process comprising at least one of a solid phase carbon coating, a liquid phase carbon coating, and a gas phase carbon coating.
[0142] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material.
[0143] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, the carbon source gas being a hydrocarbon.
[0144] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain an anode material, the carbon source gas including at least one of methane, ethylene, acetylene, propyne, propene, propane, toluene, benzene, styrene, and phenol.
[0145] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, wherein the pyrolysis temperature is 600°C to 1000°C.
[0146] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, wherein the heating temperature of the silicon-oxygen material is 500°C to 1200°C, and the heat retention time is 0.5h to 20h.
[0147] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, and the reaction gas pressure of the pyrolysis is 1.0 atm to 10.0 atm.
[0148] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas, a carbon source gas and an auxiliary gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, wherein the auxiliary gas includes H2.
[0149] In some possible embodiments, the method further includes: after heating the silicon-oxygen material, introducing a protective gas, a carbon source gas and an auxiliary gas, and thermally decomposing the carbon source gas to obtain a negative electrode material, wherein the molar ratio of the carbon source gas to the auxiliary gas is (2-10):1.
[0150] In some possible embodiments, the method further comprises: mixing the silicon-oxygen material with a solid-phase carbon source to obtain a negative electrode material by carbonization.
[0151] In some possible embodiments, the method further includes carbonizing the mixture obtained by mixing the silicon-oxygen material and the solid-phase carbon source to obtain a negative electrode material, the temperature of the carbonization is 500°C to 1000°C, and the time of the carbonization is 2h to 20h.
[0152] In some possible embodiments, the method further comprises: subjecting the mixture obtained by mixing the silicon-oxygen material with a solid-phase carbon source to a carbonization process to obtain a negative electrode material, the solid-phase carbon source comprising at least one of a sugar, an ester, a hydrocarbon, an organic acid, and a polymer.
[0153] In some possible embodiments, the method further comprises: subjecting the mixture obtained by mixing the silicon-oxygen material with a solid-phase carbon source to a carbonization process to obtain an anode material, the solid-phase carbon source comprising at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin.
[0154] In some possible embodiments, the method further comprises: mixing the silicon-oxygen material with a solid-phase carbon source to obtain a negative electrode material by carbonization, and the mass ratio of the solid-phase carbon source to the silicon-oxygen material is 5:(5-95).
[0155] In some possible embodiments, the method further includes coating the silicon-oxygen material with a coating solution containing a flexible polymer to obtain a negative electrode material.
[0156] In some possible embodiments, the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer.
[0157] In some possible embodiments, the flexible polymer comprises any one or a combination of at least two of polyolefins and their derivatives, polyvinyl alcohol and its derivatives, polyacrylic acid and its derivatives, polyamides and its derivatives, carboxymethylcellulose and its derivatives, and alginic acid and its derivatives.
[0158] In some possible embodiments, the flexible polymer has a weight average molecular weight of 2,000 to 1,000,000.
[0159] In some possible embodiments, the flexible polymer comprises a thermally crosslinkable functional group, the thermally crosslinkable functional group comprising any one or a combination of at least two of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond.
[0160] In some possible embodiments, the flexible polymer is polyolefins and their derivatives, or combinations of polyolefins and their derivatives with alginic acid and its derivatives.
[0161] In some possible embodiments, the coating liquid contains a solvent, and the solvent is any one or a combination of at least two selected from water, methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons.
[0162] In some possible embodiments, the coating liquid comprises an antisolvent, the antisolvent being a poor solvent for the flexible polymer.
[0163] In some possible embodiments, the coating liquid includes an anti-solvent, and the anti-solvent is any one or a combination of at least two selected from methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons.
[0164] In some possible embodiments, the step of performing a coating process on the silicon-oxygen material using a coating solution containing the flexible polymer includes adding a silicon-oxygen material to the coating solution of the flexible polymer, stirring, and separating to obtain a negative electrode material precursor, and performing a heat treatment on the negative electrode material precursor.
[0165] In some possible embodiments, the step of coating the silicon-oxygen material with a coating solution containing the flexible polymer includes adding a silicon-oxygen material to the coating solution of the flexible polymer, stirring and separating to obtain a negative electrode material precursor, and subjecting the negative electrode material precursor to a heat treatment, the temperature of the heat treatment being 100°C to 400°C, and the time of the heat treatment being 2h to 12h.
[0166] In some feasible embodiments, the step of coating the silicon-oxygen material with a coating solution containing the flexible polymer includes adding a silicon-oxygen material to the coating solution of the flexible polymer, stirring and separating to obtain a negative electrode material precursor, and subjecting the negative electrode material precursor to a heat treatment, wherein the stirring temperature is 20°C to 100°C, and the stirring time is 1 to 24 hours.
[0167] In some possible embodiments, the coating liquid further comprises a conductive material.
[0168] In some possible embodiments, the coating liquid further includes a conductive material, and the conductive material includes flake graphite and a nano-carbon-based material.
[0169] In some possible embodiments, the coating solution further comprises a water-insoluble lithium silicate.
[0170] In some possible embodiments, the coating solution further includes a water-insoluble lithium silicate, and the water-insoluble lithium silicate includes at least one of Li2SiO3 and Li2Si2O5.
[0171] No. 5 In an aspect, the present application provides a lithium ion battery, the lithium ion battery comprising the negative electrode material described above or the negative electrode material obtained by the method described above. Effect of the Invention
[0172] The solution of the present application has at least the following advantageous effects:
[0173] The silicon oxide material according to the present invention includes silicon oxide, which is a primary particle of spherical silicon oxide with a Wadell sphericity of greater than 0.92, and the spherical particles have isotropic characteristics, so that they contract and expand uniformly outward along the radial direction during the circulation process, and can maintain the stability of the structure under isotropic stress, and there is no "weak point" of stress due to the uneven shape, so that the possibility of electrolyte penetrating into the material due to collapse of the particle structure and rupture of the SEI film is greatly reduced, and the electrolyte penetrating into the material and continuing to generate a new SEI film is effectively avoided, and the repeated fracture and generation of the SEI film is avoided, the volume expansion of the material is reduced, and the cycle performance of the material is improved. In addition, the specific surface area of the spherical particles is the smallest among particles of the same volume, and the SEI film generated during the circulation process is the smallest, so that the irreversible charge capacity is effectively reduced, and the irreversible capacity loss during the circulation process can be further reduced.
[0174] The present invention employs a plasma method or atomization method to prepare silicon-oxygen material or anode material, by first melting the raw material to obtain a droplet-like product, and then forming primary particles of silicon-oxygen material with high sphericity during the cooling process, thus solving the technical problem of the volume expansion of silicon oxide, and the preparation method is simple, easy to operate, and suitable for mass production. [Brief description of the drawings]
[0175] [Figure 1] 1 is a process flow chart of a method for producing a negative electrode material according to an embodiment of the present application. [Figure 2a]1 is an electron microscope photograph of the silicon-oxygen material produced in Example 1 of the present application. [Figure 2b] 1 is a cross-sectional electron microscope photograph of the silicon-oxygen material produced in Example 1 of the present application. [Diagram 3] 1 is an electron microscope photograph of the silicon-oxygen material produced in Example 1 of the present application. [Figure 4a] 1 is an electron microscope photograph of the silicon-oxygen material produced in Example 3 of the present application. [Figure 4b] 1 is a cross-sectional electron microscope photograph of a silicon oxygen material produced in Example 3 of the present application. [Figure 5a] 1 is an electron microscope photograph of the silicon-oxygen material prepared in Example 4 of the present application. [Figure 5b] 1 is a cross-sectional electron microscope photograph of the silicon-oxygen material produced in Example 4 of the present application. [Figure 6] 1 is an electron microscope photograph of the negative electrode material prepared in Example 10 of the present application. [Figure 7a] FIG. 2 is a SEM cross-sectional view of a primary particle of a silicon oxygen material produced in Example 12 of the present application. [Figure 7b] FIG. 2 is a distribution diagram of Si element in the primary particles of the silicon-oxygen material produced in Example 12 of the present application. [Figure 7c] FIG. 2 is a distribution diagram of O element in the primary particles of the silicon-oxygen material produced in Example 12 of the present application. [Figure 7d] FIG. 2 is a distribution diagram of Mg element in the primary particles of the silicon-oxygen material prepared in Example 12 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0176] The following are preferred embodiments of the present invention, and it should be noted that those skilled in the art may make some improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
[0177] [First aspect] Embodiments of the present application provide a silicon-oxygen material, which contains silicon oxide, the chemical formula of the silicon oxide is SiOx (0 < x < 2), the silicon-oxygen material is a primary particle, and the Wadell sphericity of the primary particle is greater than 0.92.
[0178] The silicon-oxygen material of this embodiment is a primary particle of silicon oxide with a Wadell sphericity greater than 0.92. When used as a negative electrode material, its structure is more stable during the cycling process, and it can avoid the problem of particle crushing of the material due to the repeated formation of the SEI film, which helps to improve the cycle performance of the material and reduce the volume expansion caused by the formation of the SEI film. In the prior art, only spheroidization treatment is performed on single silicon or silicon dioxide, and the spheroidization technology of silicon oxide is currently difficult. The high spheroidization of silicon oxide (sphericity greater than 0.92) is even more difficult. In the present application, through a large number of tests and process optimization, the inventors can make the sphericity of the produced silicon oxide reach 0.92 or more, which has a more stable structure during the cycling process and can avoid the problem of particle crushing of the material due to the repeated formation of the SEI film, showing an unexpected effect.
[0179] Specifically, the Wadell sphericity of the primary particles of silicon oxide may be 0.925, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, etc. As can be understood, the Wadell sphericity of the primary particles of silicon oxide is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0180] The silicon-oxygen material according to the embodiments of the present application further contains at least one of a reducing metal and a reducing metal compound.
[0181] In the above-mentioned solution, compared with the primary particles of simple silicon oxide, the reducing metal and / or reducing metal compound in the silicon-oxygen material can reduce the consumption of lithium escaping from the positive electrode material during the first charge of the material, and the lithium ion battery produced can greatly reduce the consumption of irreversible charging lithium, and has a high charge / discharge specific capacity and excellent first coulombic efficiency. For example, when the reducing metal is lithium element, the pre-lithiated material pre-lithiates the silicon-based material in advance, so that the size of the silicon crystal grains in the material is significantly larger than that of the conventional silicon-based material, which may cause deterioration of the cycle performance. A material with high sphericity can improve the cycle performance by improving the structural stability. As a result of the comprehensive action of both, the material can have high effect and simultaneously achieve cycle performance, and the overall performance of the entire material is excellent.
[0182] Specifically, the Wadell sphericity of the primary particles may be 0.925, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, etc. As can be appreciated, the Wadell sphericity of the primary particles is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0183] In some embodiments, the Wadell sphericity of the primary particles of the silicon oxygen material is greater than 0.95.
[0184] In some embodiments, the reducing metal comprises at least one of an alkali metal, an alkaline earth metal, and a transition metal.
[0185] Specifically, the reducing metal element is at least one selected from the group consisting of Li, K, Mg, Al, Ca, Zn, Na, and Ti.
[0186] In some embodiments, the mass content of oxygen element in the silicon-oxygen material is 10% to 50%, and specifically may be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 48%, or 50%, etc., but is not limited thereto.
[0187] In some embodiments, the mass content of the reducing metal element in the silicon-oxygen material is 0.5% to 50%, and specifically may be 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%, etc., but is not limited thereto.
[0188] In some embodiments, the mass content of silicate in the silicon-oxygen material is 10% to 80%, and may be specifically, but not limited to, 10%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, or 80%, etc.
[0189] In some embodiments, in the element distribution map obtained by scanning the SEM cut surface of the primary particles of the silicon-oxygen material with X-rays, the distribution surface of Si, O and reducible metal elements is in a uniformly dispersed state. In the silicon-oxygen material, Si, O and reducible metal elements are uniformly distributed in the primary particles, which can effectively prevent components such as air from penetrating into the primary particles and causing the active components to become ineffective, and the structure and properties of the material do not deteriorate during long-term storage, which is very suitable for lithium-ion batteries. The main advantage of uniform dispersion is that it ensures that the materialization state of each part inside the material is similar (i.e., silicate concentration, silicon grain size, etc.), so that the expansion and contraction of each part during the lithium release process are all at the same level, and there is no stress vulnerability caused by local expansion being too large, which allows the material to exhibit better performance.
[0190] In some embodiments, the reducible metal compound comprises at least one of a reducible metal oxide, a reducible metal silicide, and a reducible metal silicate.
[0191] In some embodiments, the reducible metal compound comprises a reducible metal silicate, and the reducible metal silicate is uniformly distributed within the primary particles.
[0192] In some embodiments, the silicate comprises lithium silicate, ie, the reducing metal element is Li.
[0193] In some embodiments, the lithium silicate comprises at least one of Li2SiO3, Li4SiO4, Li2Si2O5, and Li2Si3O7. Preferably, the lithium silicate is Li2Si2O5.
[0194] In some embodiments, the silicate comprises crystalline Li2Si2O5, and the grain size of Li2Si2O5 is smaller than 20 nm. By controlling the grain size of the silicate produced, the silicon-oxygen material finally obtains a high initial coulombic efficiency and at the same time improves the cycling performance of the material. In addition, silicate (especially lithium silicate) has good lithium ion conductive properties, and by combining the smaller grain size, it can better ensure that the lithium ions can smoothly complete the lithium absorption and release reaction, and shows good multiplication performance and high safety.
[0195] In some embodiments, the silicate comprises crystalline Li2Si2O5, and the mass content of Li2Si2O5 in the silicon-oxygen material is 20% to 80%, specifically, it may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, or 80%, etc., but is not limited thereto.
[0196] In some embodiments, the molar ratio of Si to Li in the silicon-oxygen material is (1 to 50):1, and may be specifically, but not limited to, 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, or 50:1.
[0197] In some embodiments, silicate is dispersed in silicon oxide, which can alleviate the problem of volume expansion during charging and discharging of silicon. The spherical structure can further improve the structural stability of the material, which has excellent cycle performance and small volume effect, thereby providing excellent electrochemical performance.
[0198] In some embodiments, the silicon oxygen material further comprises a non-metallic doping element, such as N, S, P, and the like.
[0199] In some embodiments, the Wadell sphericity of the primary particles is greater than 0.95.
[0200] In some embodiments, the D of the silicon oxygen material 50 D 50 ≦50μm. Specifically, D 50 may be 50 μm, 45 μm, 40 μm, 38 μm, 35 μm, 33 μm, 30 μm, 25 μm, 20 μm, 15 μm, 10 μm, 8 μm, 6 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0201] In some embodiments, the particle size distribution of the silicon oxygen material is greater than or equal to 3 μm. <D 50 <10μm, 2μm≦D 10 ≦5μm and 0.8≦(D 90 -D 10 ) / D 50 ≦1.2. The particle size of the primary particles of the silicon-oxygen material can be controlled within a suitable micron range to prevent the large specific surface area and oxidation problems of the silicon-oxygen material caused by the particle size being too small, both of which result in a decrease in capacity and initial efficiency. (D 90 -D 10 ) / D 50 represents the particle size distribution of the material. The narrow particle size distribution can greatly reduce the proportion of fine powder and large particles in the material, avoid the fine powder removal process in the subsequent reprocessing process, improve the cycle performance of the product, improve the expansion rate, high temperature storage and high temperature cycle, and the relatively low proportion of large particles can improve the cycle, so that the material has excellent cycle, expansion, high temperature storage and high temperature cycle performance. Specifically, D 50 may be 3.5 μm, 4 μm, 6 μm, 8 μm, or 9.5 μm, and D 10 may be 2 μm, 4 μm, or 5 μm, (D90 -D 10 ) / D 50 may be 0.8, 0.9, 1.0, 1.1, 1.2, but is not limited to the recited values; other unrecited values within the numerical range are equally applicable.
[0202] In some embodiments, the specific surface area of the silicon oxygen material is greater than 10 m 2 / g and the specific surface area is less than 10m 2 If the specific surface area is greater than 0.2 m / g, the capacity and initial efficiency are reduced, which affects the performance of the battery. 2 / g, 0.6m 2 / g, 1.0m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.6m 2 / g, 4.0m 2 / g, 4.2m 2 / g, 4.6m 2 / g, 5m 2 / g, 5.2m 2 / g, 5.5m 2 / g, 5.8m 2 / g, 6.0m 2 / g, 6.2m 2 / g, 6.8m 2 / g, 7.0m 2 / g, 7.4m 2 / g, 8.0m 2 / g, 8.5m 2 / g, 9.2m 2 / g or 9.8m 2 / g, but is not limited to the recited values; other unrecited values within the range are equally applicable.
[0203] In some embodiments, the Si crystallite size in the silicon oxide material is 20 nm or less. Specifically, the Si crystallite size in the silicon oxide may be 20 nm, 18 nm, 15 nm, 12 nm, 10 nm, 9.2 nm, 8 nm, 6.7 nm, 6 nm, 5 nm, 3 nm, etc., but is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0204] In some embodiments, the Si crystallite size in the silicon oxide is 10 nm or less. The size of the Si crystallite reflects the degree of disproportionation of the silicon oxide, and the larger the size of the Si crystallite, the higher the degree of disproportionation, which produces a large amount of Si crystallite and SiO2, which leads to problems such as larger volume expansion due to the simple Si and capacity reduction due to the lack of capacity of SiO2, which is disadvantageous to the excellent performance of SiO itself.
[0205] It should be noted that the silicon-oxygen materials of the above embodiments can be arbitrarily combined, provided that they are not inconsistent with each other, such as by combining and limiting the specific surface area and the Si crystallite size.
[0206] [Second aspect] The present application provides an anode material, the anode material comprising a silicon oxygen material of a first aspect.
[0207] When the above silicon-oxygen material is used as the negative electrode material, it has a more stable structure during cycling, which helps to avoid the crushing of material particles caused by the repeated formation of the SEI film, improve the cycling performance of the negative electrode material, and reduce the volume expansion caused by the formation of the SEI film.
[0208] It should be noted that the negative electrode material is not limited to only containing the silicon oxide material. In some preferred embodiments, based on the design of the negative electrode material, other materials can be added and blended with the silicon oxide to optimize the performance of the negative electrode material in various aspects.
[0209] In some embodiments, the negative electrode material further comprises a carbon layer coated on the surface of the silicon oxygen material.
[0210] As can be seen, the silicon-oxygen material core in the negative electrode material has a high spherical degree, and the carbon material can be more uniformly coated when carbon coating is performed, the thickness of the carbon layer is more uniform, and there are fewer exposed primary particles of the silicon-oxygen material and weak spots in the carbon layer, which is helpful in improving the cycle stability of the negative electrode material.
[0211] In some embodiments, the difference between the maximum and minimum thicknesses of the carbon layer is less than the minimum thickness.
[0212] In some embodiments, the thickness of the carbon layer is 10 nm to 500 nm, and more preferably 50 nm to 200 nm. Specifically, the thickness of the carbon layer may be 10 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, 300 nm, 400 nm, or 500 nm, but is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0213] In some embodiments, the negative electrode material D 50 D 50 ≦100μm. Specifically, the negative electrode material D 50 may be 100 μm, 90 μm, 80 μm, 70 μm, 65 μm, 60 μm, 58 μm, 55 μm, 50 μm, 48 μm, 40 μm, 35 μm, 30 μm, 25 μm, 20 μm, 15 μm, or 10 μm, etc., but is not limited to the recited numerical values, and other unrecited numerical values within the numerical range are equally applicable.
[0214] In some embodiments, the negative electrode material may further include silicon.
[0215] In some embodiments, the negative electrode material may further include silicon and lithium containing compounds.
[0216] In some embodiments, the negative electrode material further comprises silicon and lithium silicate, the lithium silicate further comprising at least one of Li2SiO3, Li4SiO4, Li2Si2O5, and Li2Si3O7.
[0217] In some embodiments, when the silicon-oxygen material is used as a negative electrode material, the negative electrode material may further include a metal compound, which includes at least one of a metal oxide, a metal silicide, and a metal silicate.
[0218] In some embodiments, the negative electrode material further comprises a carbon material, and the silicon oxygen material is dispersed in the carbon material.
[0219] The silicon-oxygen material is dispersed in the carbon material, and the carbon material forms a conductive network for the silicon-oxygen material, which overcomes the drawback of the silicon-oxygen material having low electrical conductivity and helps the silicon-oxygen material to exert its capacity and stabilize its cycle.
[0220] In another embodiment, the anode material comprises a silicon oxygen material and a carbon material, the silicon oxygen material being dispersed in the carbon material, the anode material being spherical particles, and the Wadell sphericity of the anode material is greater than 0.3.
[0221] The negative electrode material has a high degree of sphericity, the silicon-oxygen material can expand uniformly in all directions during the expansion process, the expansion stress is uniformly distributed, and at the same time, the spherical structure is stable, and the particles are not easily broken during the long cycle process. The existence of protruding parts of the particles is a weak point that is easily broken, and the spherical structure avoids the existence of this structure, so that the SEI film grows slowly during the long cycle process and the expansion rate is low, and the carbon material overcomes the disadvantage of the low electrical conductivity of the silicon-oxygen material, which is helpful for the silicon-oxygen material to exert its capacity and stabilize its cycle.
[0222] Specifically, the wadell sphericity of the negative electrode material may be 0.31, 0.35, 0.40, 0.42, 0.45, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9, 0.95, etc., and as can be understood, the wadell sphericity of the negative electrode material is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0223] In some embodiments, the silicon oxygen material is uniformly dispersed in the carbon material.
[0224] In some embodiments, the carbon material coats the silicon oxygen material.
[0225] In some embodiments, the Wadell sphericity of the negative electrode material is greater than 0.5.
[0226] In some embodiments, the wadell sphericity of the negative electrode material is greater than 0.92. Specifically, the wadell sphericity of the negative electrode material may be 0.925, 0.93, 0.94, 0.95, 0.96, 0.97, etc. When the sphericity of the negative electrode material is in this range, it can ensure that SiOx expands uniformly in all directions during the expansion process, and the expansion stress is uniformly distributed. At the same time, the spherical structure is stable, and the particles are not easily broken during the long cycle process. The existence of protruding points of the particles is a weak point that is easily broken, and the spherical structure avoids the existence of this structure, effectively avoiding the repeated growth and fracture of the SEI film during the long cycle process.
[0227] In some embodiments, in the silicon oxygen material, the mass of the oxygen element is 0% to 67% (but not including 0%) of the sum of the silicon element and the oxygen element. Specifically, the mass of the oxygen element may be 0.5%, 1%, 5%, 10%, 15%, 18%, 21%, 28%, 30%, 37%, 42%, 47%, 50%, 55%, 60% or 67% of the sum of the silicon element and the oxygen element. As can be understood, the ratio of the mass of the oxygen element to the sum of the silicon element and the oxygen element is not limited to the recited numerical values, and other numerical values not recited within the numerical range are applicable as well.
[0228] In some embodiments, the negative electrode material spherical particles have a silicon oxide D 50 D 50 The smaller the particle size of silicon oxide, the higher the degree of dispersion in the carbon material. 50 may be 1.5 μm, 1.2 μm, 1 μm, 0.8 μm, 0.5 μm, 0.4 μm, 0.2 μm or 0.1 μm. As can be seen, the D of silicon oxide 50 is not limited to the recited numerical values; other unrecited numerical values within the numerical range are equally applicable.
[0229] In some embodiments, the Si crystallite size in the silicon oxide is 50 nm or less. The smaller the Si crystallite size, the better the cycle performance of the silicon oxide and the lower the expansion coefficient. Specifically, the Si crystallite size in the silicon oxide may be 50 nm, 46 nm, 40 nm, 38 nm, 34 nm, 30 nm, 28 nm, 25 nm, 23 nm, 20 nm, 16 nm, 13 nm, 10 nm, 7 nm, 5 nm, or 3.8 nm, etc., and as can be understood, the Si crystallite size in the silicon oxide is not limited to the recited values, and other values not recited within the numerical range are equally applicable. Preferably, the Si crystallite size in the silicon oxide is 20 nm or less, and more preferably, the Si crystallite size in the silicon oxide is 10 nm or less.
[0230] In some embodiments, the negative electrode material D 50 D 50 The smaller the particle size of the negative electrode material, the less likely it is to be crushed and the lower the expansion coefficient. 50 may be 40 μm, 35 μm, 33 μm, 30 μm, 27 μm, 24 μm, 21 μm, 18 μm, 15 μm, 13 μm, 10 μm, 7 μm, 5 μm, 3 μm, or 1.5 μm, etc. As can be appreciated, the D 50 is not limited to the recited numerical values; other unrecited numerical values within the numerical range are equally applicable.
[0231] In some embodiments, the porosity of the negative electrode material is less than 20%. The smaller the porosity, the tighter the contact between the carbon material and the silicon oxide and the structural stability is, which is helpful for the capacity performance and cycle stability of the negative electrode material. Specifically, the porosity of the negative electrode material may be 19.2%, 18%, 15%, 13%, 10%, 8%, 5%, 3%, 2%, etc. As can be understood, the porosity of the negative electrode material is not limited to the recited values, and other values not recited within the numerical range are equally applicable.
[0232] In some embodiments, the silicon oxide material comprises 40% to 95% of the mass of the negative electrode material. Specifically, the mass fraction of the negative electrode material that is silicon oxide may be 40%, 45%, 50%, 58%, 60%, 63%, 67%, 70%, 74%, 78%, 80%, 85%, 90%, 93%, or 95%. As can be appreciated, the mass fraction of the negative electrode material that is silicon oxide is not limited to the recited values, and other unrecited values within the range are equally applicable.
[0233] In some embodiments, the carbon material comprises amorphous carbon.
[0234] In some embodiments, the anode material further comprises graphite, which is dispersed in the carbon material, the addition of graphite serving to improve the electrical conductivity and initial coulombic efficiency of the system.
[0235] In some embodiments, when the total mass of the negative electrode material is 100%, the mass fraction of graphite is 0% to 40%, the mass fraction of silicon oxide is 40% to 95%, and the mass fraction of the carbon material is 5% to 60%.
[0236] Additionally, the graphite includes at least one of natural graphite, synthetic graphite, and mesocarbon microbeads.
[0237] In another embodiment, the negative electrode material comprises a silicon oxygen material and a carbon material, and is grown in situ on a surface of the silicon oxygen material, and the carbon material has a graphene structure, and the silicon oxygen material is uniformly dispersed in the carbon material having the graphene structure.
[0238] In some embodiments, the negative electrode material has a carbon characteristic peak D, a carbon characteristic peak G, a silicon characteristic peak A, and a graphene characteristic peak B in the Raman spectrum.
[0239] In some embodiments, the peak intensity I of the silicon characteristic peak A A and the peak intensity of graphene characteristic peak B, I B Comparison with I A / I B is 0.1 to 50, and specifically may be 0.1, 0.5, 0.8, 1, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, or 50, etc. A / I B If the ratio is too large, too much SiO is exposed on the surface of the primary particles, the carbon coating is incomplete, the conductivity of the negative electrode material is reduced, and it is difficult to exhibit electrochemical performance. A / I B If the ratio is too small, the carbon coating layer will be too thick, reducing the specific capacity of the material.
[0240] In some embodiments, the peak intensity I of the carbon characteristic peak D D and the peak intensity I of the carbon characteristic peak G. G Comparison with I D / I G is 0.5 to 2.0, specifically, may be 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, or 2.0, etc., and I D / I G If the ratio is too large, the initial efficiency of the composite anode material decreases. D / I G If the ratio is too small, the multiplier performance of the composite negative electrode material will decrease.
[0241] In some embodiments, the peak intensity I of the graphene characteristic peak B B and the peak intensity of carbon characteristic peak D. D Comparison with I B / I D is 0 to 1, and specifically may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, or the like.
[0242] In another embodiment of the negative electrode material, the negative electrode material comprises a silicon-oxygen material and a carbon material, the silicon-oxygen material is dispersed in the carbon material, the negative electrode material is a secondary particle, and the Wadell sphericity of the negative electrode material is greater than 0.91. When the sphericity of the silicon-oxygen material is high, the structure is more stable when forming the secondary particle, and when the sphericity of both the secondary particle and the silicon-oxygen material is very high, the stability of the structure of the negative electrode material as a whole secondary particle is ensured.
[0243] In some embodiments, the silicon oxygen material is a primary particle of silicon oxide.
[0244] In some embodiments, the volume of silicon oxide powder having a particle size of 1.0 μm or less accounts for 15% or less of the total silicon oxide.
[0245] In some embodiments, the grain size distribution of the silicon oxide is D 90 <25.0μm, D 10>0.5μm and 1μm≦D 50 ≦10μm. The particle size of the primary particles of the silicon-oxygen material can be controlled within a suitable micron range to prevent the large specific surface area and oxidation problems of the silicon-oxygen material caused by the particle size being too small, both of which result in a decrease in capacity and initial efficiency. Specifically, D 90 may be 3.5 μm, 4 μm, 6 μm, 8 μm, 9.5 μm, 15 μm, 19.5 μm, 20.5 μm, 23.5 μm, or 24.5 μm, etc., and D 10 may be 0.5 μm, 0.8 μm, 1.0 μm, 2 μm, 4 μm, or 5 μm, and D 50 may be 1.0 μm, 1.2 μm, 2.0 μm, 4.5 μm, 5.5 μm, 7.5 μm, 8.5 μm, or 10 μm, but is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0246] In some embodiments, the Si crystallite size in the silicon oxide is 1.0 nm to 20 nm. Specifically, the Si crystallite size in the silicon oxide may be 20 nm, 18 nm, 15 nm, 12 nm, 10 nm, 9.2 nm, 8 nm, 6.7 nm, 6 nm, 5 nm, 3 nm, or 1.0 nm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0247] In some embodiments, the specific surface area of the negative electrode material is less than 0.5 m 2 / g~50m 2 / g, and the specific surface area of the negative electrode material is specifically 0.5 m 2 / g, 0.6m 2 / g, 1.0m 2 / g, 1.5m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.6m 2 / g, 4.0m 2 / g, 4.6m 2 / g, 5m 2 / g, 5.5m 2 / g, 5.8m 2 / g, 6.0m 2 / g, 6.8m 2 / g, 7.0m 2 / g, 7.4m 2 / g, 8.0m 2 / g, 8.5m 2 / g, 9.8m 2 / g, 15m 2 / g or 50m 2 / g, but is not limited to the recited values; other unrecited values within the range are equally applicable.
[0248] In some embodiments, the tap density of the negative electrode material is less than or equal to 0.5 g / cm 3 ~5.0g / cm 3 Specifically, 0.5 g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 2.0g / cm 3 , 2.5g / cm 3 , 3.0g / cm 3 , 3.5g / cm 3 , 4.0g / cm 3 or 5.0 g / cm 3 etc., and of course may be other values within the above ranges, and are not limited thereto. As can be appreciated, controlling the tap density of the negative electrode material within the above ranges helps to improve the energy density of the material.
[0249] In some embodiments, the particle size D of the negative electrode material 50 is the grain size of silicon oxide D 50 The particle diameter D of the negative electrode material is 2 to 10 times, specifically, it may be 2 times, 3 times, 5 times, 7 times, 8 times, 10 times, etc. 50 is the grain size of silicon oxide D 50 It is 2 to 5 times that.
[0250] In some embodiments, the particle size of the negative electrode material is 20 μm≦D 90 ≦50μm, 5μm <D50 <20μm and 2μm≦D 10 ≦5μm. Specifically, D 90 may be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm, etc., and D 10 may be 2 μm, 2.5 μm, 3 μm, 4 μm or 5 μm, and D 50 may be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, or 20 μm, but is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0251] In some embodiments, the mass content of carbon element in the negative electrode material is 2% to 20%, and specifically may be 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc., and of course may be other values within the above range, and is not limited thereto.
[0252] In some embodiments, the porosity of the negative electrode material is 1% to 50%, and the porosity of the negative electrode material may be specifically 1%, 5%, 10%, 20%, 35%, 48%, or 50%, etc., and of course may be other values within the above range, and is not limited thereto. As can be understood, a suitable porosity helps to alleviate the volume expansion of the negative electrode material. If the porosity is too high, it will significantly reduce the volume energy density of the material. Preferably, the porosity of the negative electrode material is 2% to 20%.
[0253] The present application provides an anode material, the anode material comprising a silicon oxygen material of a first aspect and a coating layer located on a surface of the silicon oxygen material, the coating layer comprising a flexible polymer.
[0254] In the above-mentioned solution, the coating layer is coated on the surface of the silicon-oxygen material, and the flexible polymer effectively prevents the contact between the water in the electrolyte and the silicon-oxygen material, generates alkalinity, improves the processing stability problem of the silicon-oxygen material, and does not affect the water-based processing performance of the material. In addition, the flexible polymer can more effectively suppress the expansion of the silicon-based material, so that the electrical conductivity of the anode material is high and the electrical conductivity is stable. Therefore, the silicon-based anode material of the present application is very suitable for lithium-ion batteries and has excellent cycle expansion performance.
[0255] In some embodiments, the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer.
[0256] In some embodiments, the flexible polymer comprises at least one of polyolefins and their derivatives, polyvinyl alcohol and its derivatives, polyacrylic acid and its derivatives, polyamides and its derivatives, carboxymethylcellulose and its derivatives, and alginic acid and its derivatives.
[0257] In the present application, the term "natural flexible polymer and / or synthetic flexible polymer" refers to a natural flexible polymer, a synthetic flexible polymer, or a mixture of a natural flexible polymer and a synthetic flexible polymer.
[0258] Typical, but non-limiting examples of combinations of flexible polymers include combinations of polyolefins and polyvinyl alcohol, combinations of polyvinyl alcohol and carboxymethylcellulose, combinations of carboxymethylcellulose and alginic acid, combinations of polyamides and derivatives of carboxymethylcellulose, combinations of polyolefins, polyolefin derivatives and polyacrylic acid, combinations of polyvinyl alcohol, polyamide derivatives and alginic acid, combinations of polyolefins, polyvinyl alcohol, polyacrylic acid derivatives, polyamides and alginic acid, etc.
[0259] In some embodiments, the flexible polymer comprises polyolefins and their derivatives, combinations of polyolefins and their derivatives with alginic acid and its derivatives.
[0260] In some embodiments, the flexible polymer comprises polycarbonate.
[0261] In some embodiments, the weight average molecular weight of the flexible polymer is 2000 to 1000000, for example, 2000, 5000, 10000, 15000, 20000, 30000, 40000, 50000, 60000, 75000, 100000, 200000, 300000, 350000, 400000, 500000, 600000, 650000, 700000, 800000, 900000, or 1000000, etc., and is preferably 100000 to 500000.
[0262] In some embodiments, the flexible polymer includes a thermal crosslinking functional group (also called a thermal crosslinkable functional group), and the thermal crosslinking functional group includes at least one of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond. As can be understood, the thermal crosslinking functional group undergoes a crosslinking reaction under a condition of being heated to a certain temperature. As can be understood, crosslinking (also called a crosslinking reaction) is a relatively stable molecular (body-type molecular) reaction in which two or more molecules are bonded to each other and crosslinked into a network structure, and the crosslinking reaction can be divided into physical crosslinking, chemical crosslinking, etc. according to the trigger factor, and is not limited here.
[0263] In some embodiments, the cover layer further comprises an electrically conductive material.
[0264] In some embodiments, the conductive material includes flake graphite and nano-carbon based materials.
[0265] In some embodiments, flake graphite is attached to the surface of the silicon-oxygen material, a flexible polymer is coated on the surface of the silicon-oxygen material and the flake graphite, a nano-carbon material is filled in the area of the surface of the silicon-oxygen material that is not attached by the flake graphite, and / or a nano-carbon material is filled in the area of the surface of the silicon-oxygen material that is not covered by the flexible polymer. The cooperation of the flake graphite attached to the surface of the silicon-oxygen material, the flexible polymer and the lithium silicate coated on the surface of the silicon-oxygen material and the flake graphite, and the nano-carbon material filled in the void area can effectively suppress the expansion of the silicon-oxygen material, and at the same time, the bonding of the flake graphite and the filling of the void area with the nano-carbon material make the performance of the negative electrode material after coating excellent, effectively suppress the cycle expansion performance, and extend the service life of the lithium-ion battery.
[0266] In some embodiments, the scale graphite includes natural flake graphite and / or artificial flake graphite. In the present application, "natural flake graphite and / or artificial flake graphite" refers to natural flake graphite, artificial flake graphite, or a mixture of natural flake graphite and artificial flake graphite.
[0267] In some embodiments, the conductive material comprises a combination of flake graphite and nano-carbon-based material. When the conductive material is just a mixture of these two materials, the two materials can be blended with the silicon-based composite material to suppress the expansion of the silicon-based material, and further improve the electrical conductivity and electrical stability.
[0268] In some embodiments, the nano-carbon-based material comprises at least one of conductive graphite, graphene, carbon nanotubes, and carbon nanofibers.
[0269] In one possible embodiment, the conductive material may further include a conductive metal, a conductive alloy, etc. The conductive metal may be, for example, copper, aluminum, silver, gold, etc., and the conductive alloy may be, for example, a copper-zinc alloy, a copper-aluminum alloy, a titanium-zinc alloy, an aluminum-copper-zinc alloy, etc. As can be understood, when the conductive material includes these metal substances, these metal substances are also doped into the coating layer coated on the surface of the silicon-oxygen material, thereby further improving the electrical conductivity.
[0270] In some embodiments, the coating layer further comprises a water-insoluble lithium silicate, which can effectively prevent the contact between the water in the electrolyte and the silicon-oxygen material and generate alkalinity, and the coated silicon-oxygen material is easily dissolved in water or exhibits strong alkalinity, and does not affect the water-based processing performance of the material.
[0271] In some embodiments, the water insoluble lithium silicate comprises at least one of Li2SiO3 and Li2Si2O5.
[0272] In some embodiments, the mass percentage of the flexible polymer is 0-10% (but not including 0) when the total mass of the silicon oxygen material is 100%, such as 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6.5%, 8%, 9%, or 10%, and preferably 3-7%.
[0273] In some embodiments, when the total mass of the silicon-oxygen material is 100%, the mass percentage of the flake graphite is 0 to 20% (but not including 0), for example, 0.5%, 1%, 3%, 3.5%, 5%, 6%, 8%, 10%, 12%, 13%, 15%, 16%, 18%, or 20%, and preferably 5 to 10%.
[0274] In some embodiments, when the total mass of the silicon-oxygen material is 100%, the mass percentage of the nano-carbon material is 0 to 5% (excluding 0), for example, 0.5%, 1%, 2%, 2.5%, 3%, 4% or 5%, etc., and preferably 1 to 3%.
[0275] In some embodiments, the thickness of the coating layer is 10 nm to 5000 nm, and the thickness of the coating layer may be, for example, 10 nm, 20 nm, 30 nm, 50 nm, 60 nm, 70 nm, 80 nm, 100 nm, 200 nm, 300 nm, 500 nm, 1000 nm or 5000 nm, etc., and is not limited herein.
[0276] In some embodiments, the mass ratio of the coating layer in the negative electrode material is 0% to 20% (excluding 0%), for example, 0.5%, 1%, 3%, 3.5%, 5%, 6%, 8%, 10%, 12%, 13%, 15%, 16%, 18% or 20%, etc., and preferably 2% to 10%.
[0277] [Aspect 3] The examples of the present application provide a method for manufacturing a negative electrode material, and as shown in FIG. 1, include the following steps.
[0278] In S110, the raw material for manufacturing the silicon-oxygen material is heat-treated.
[0279] In S120, after cooling, a silicon-oxygen material containing silicon oxide is obtained. The chemical formula of the silicon oxide is SiOx (0 < x < 2), and the Wadell sphericity of the silicon-oxygen material is greater than 0.92.
[0280] In the above solution, the raw material for manufacturing the silicon-oxygen material is heat-treated at a high temperature to generate silicon oxide droplets at the same time. The silicon oxide droplets are cooled and automatically become spherical under the action of surface tension, and then harden into spherical silicon oxide. Since the spherical silicon oxide particles can maintain structural stability during the circulation process, the material has a low expansion rate and excellent cycle performance.
[0281] In some embodiments of the present application, the heat treatment method is to subject the raw material for producing the silicon oxygen material to a plasma reaction or to atomize the raw material for producing the material after melting. Hereinafter, these embodiments will be described respectively.
[0282] In step S210, a plasma reaction is performed on the raw material for producing the silicon oxygen material.
[0283] In step S220, the product after the reaction is cooled to obtain a silicon oxygen material containing silicon oxide. The silicon oxygen material is primary particles, the chemical formula of the silicon oxide is SiOx (0 < x < 2), and the Wadell sphericity of the primary particles is greater than 0.92.
[0284] In some embodiments, the step of S210 specifically includes conveying the raw material for producing the silicon oxygen material into the plasma flow to perform a plasma reaction.
[0285] In the above solution, the raw material enters the plasma flow and reacts at a high temperature. At the same time, silicon oxide droplets are generated. The silicon oxide droplets are cooled and automatically become spherical under the action of surface tension, and then harden into spherical silicon oxide. Since the spherical silicon oxide particles can maintain structural stability during the circulation process, the material has a low expansion rate and excellent cycle performance.
[0286] Hereinafter, the manufacturing method according to the present solution S210 - S220 will be described in detail.
[0287] Before step S210, the method further includes the following step S200. In step S200, a plasma flow is generated using a plasma generator. Here, the plasma generator is filled with a plasma generating gas.
[0288] In some embodiments, the high frequency power of the plasma generator is 50 to 100,000 kW, and in this range, low pressure and high density plasma can be generated. Specifically, the high frequency power of the plasma generator may be 50 kW, 70 kW, 100 kW, 150 kW, 200 kW, 250 kW, 500 kW, 1000 kW, 1500 kW, 2000 kW, 2500 kW, 3000 kW, 3500 kW, 4000 kW, 4500 kW, 5000 kW, 10000 kW, 20000 kW, 30000 kW, 40000 kW, 50000 kW, 60000 kW, 70000 kW, 80000 kW, 90000 kW, or 100000 kW, etc. The high frequency power of the plasma generator is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0289] In some embodiments, the DC power of the plasma generator is 2 kW to 3000 kW. Specifically, the DC power of the plasma generator may be 2 kW, 10 kW, 20 kW, 502 kW, 100 kW, 150 kW, 200 kW, 250 kW, 500 kW, 1000 kW, 1500 kW, 2000 kW, 2500 kW, 2800 kW, or 3000 kW. The DC power of the plasma generator is not limited to the recited values, and other values not recited within the numerical range are equally applicable.
[0290] In some embodiments, the plasma generating gas includes at least one of nitrogen gas and argon gas.
[0291] In some embodiments, the pressure of the plasma generating gas is controlled to 100 torr to 10,000 torr. Specifically, it may be 100 torr, 200 torr, 300 torr, 400 torr, 500 torr, 600 torr, 700 torr, 800 torr, 900 torr, 1000 torr, 2000 torr, 4000 torr, 6000 torr, 8000 torr, or 10,000 torr. However, it is not limited to the listed values, and other values not listed within the numerical range are equally applicable. By controlling the pressure of the plasma generating gas within the above range and controlling the probability of gas collision, a stable plasma can be obtained.
[0292] In some embodiments, the radial gas velocity of the plasma generating gas is 0.8 m 3 / h~100m 3 / h. The radial gas is continuously entrained to stabilize the plasma jet.
[0293] In some embodiments, the tangential gas velocity of the plasma generating gas is less than 1.0 m 3 / h~20m 3 / h. The tangential gas is used to protect the quartz tube at high discharge temperatures.
[0294] The method for generating the plasma flow is not limited to the above method.
[0295] In step S210, the raw material for producing the silicon-oxygen material is transported into the plasma flow to carry out the plasma reaction.
[0296] In some embodiments, the raw materials for producing the silicon-oxygen material include Si, SiO y and a mixture of SiO2, SiO y and Si, and a mixture of Si and SiO2, <y<2である。
[0297] In some embodiments, when the chemical formula of the produced silicon oxide is SiO, the raw materials for producing the silicon oxygen material include SiH4 and O2.
[0298] The raw material may be any material capable of producing silicon oxide in the plasma flow, and the above embodiments merely list some preferred technical solutions and do not limit the technical solutions related to the present application.
[0299] In some embodiments, the temperature in the plasma flow is between 1400° C. and 2400° C. Specifically, the plasma temperature may be 1400° C., 1450° C., 1500° C., 1550° C., 1575° C., 1600° C., 1650° C., 1700° C., 1764° C., 1800° C., 1850° C., 1900° C., 1950° C., 2000° C., 2150° C., 2200° C., 2270° C., 2300° C., or 2400° C. As can be appreciated, the temperature in the plasma flow is not limited to the recited values, and other unrecited values within the range are equally applicable.
[0300] In some embodiments, in the step of transporting the raw material into the plasma flow to carry out the plasma reaction, the raw material supply rate is 2.0g / min to 80g / min, and specifically, it can be 2.0g / min, 5.0g / min, 10.0g / min, 15g / min, 17.5g / min, 20.0g / min, 30g / min, 35g / min, 40.0g / min, 45g / min, 50g / min, 55g / min, 60.0g / min, 65g / min, 75g / min, 80.0g / min. When the particle size of the raw material particles is constant, the residence time of the raw material in the plasma flow is determined by the raw material supply rate. If the raw material supply rate is too high, the time that the raw material particles pass through the plasma flow is too short, the energy absorbed by a single particle is too low, the melting of the particles is insufficient, and the spheroidization rate of the product is further reduced. If the feed rate is too low, it can improve the spheroidization rate of the particles, but if the feed rate is too low, it will limit the yield. It is necessary to determine the appropriate feed rate based on the comprehensive influencing factors of the spheroidization rate and the yield.
[0301] In some embodiments, the step of transporting a raw material into the plasma flow to carry out a plasma reaction specifically comprises transporting a raw material for producing silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction.
[0302] In some embodiments, the carrier gas comprises at least one of nitrogen gas and argon gas.
[0303] In some embodiments, the flow rate of the carrier gas is 0.1 m 3 / h~3m 3 Specifically, the flow rate of the carrier gas is 0.1 m 3 / h, 0.5m 3 / h, 0.8m 3 / h, 1m 3 / h, 1.2m 3 / h, 1.5m 3 / h, 1.75m 3 / h, 2m 3 / h, 2.2m 3 / h, 2.6m 3 / h or 3m 3 / h, etc. If the carrier gas flow rate is too large, the radial airflow field in the plasma generator will cause the particles to fly from the high temperature area, and the axial airflow will promote the particles to fly to the cooling area after "mixing", and the two will work together to significantly reduce the spheroidization rate of the product. On the other hand, if the carrier gas flow rate is too low, the raw material will be prone to clogging the nozzle, reducing the discharge speed of the raw material, and the retention time of the raw material in the plasma torch will be too long, causing a large amount of vaporization. Therefore, an appropriate carrier gas flow rate will help the raw material to be uniformly distributed in the plasma torch, improving the spheroidization rate.
[0304] In some embodiments, the step of S210 includes using a carrier gas to transport a raw material for producing silicon oxide into the plasma flow to carry out a plasma reaction, and introducing a reducing gas. The reducing gas is SiO y This can promote the reduction of SiC and inhibit the formation of electrochemically inactive SiC.
[0305] In some embodiments, the reducing gas comprises at least one of methane and hydrogen gas.
[0306] In some embodiments, the molar ratio of the source gas to the silicon oxide is between 0 and 0.25 (but not including 0).
[0307] In some embodiments, the radial velocity of the reducing gas is less than 1 m 3 / h~10m 3 / h, specifically, 1m 3 / h, 2m 3 / h, 4m 3 / h, 5m 3 / h, 7m 3 / h, 9m 3 / h or 10m 3 / h, etc., and is not limited thereto.
[0308] In step S220, the reaction product is cooled to obtain a silicon-oxygen material containing silicon oxide.
[0309] In this embodiment, cooling is provided by a conventional water cooling system.
[0310] Further, after step S200 and before step S210, the method further includes: The raw material for producing silicon-oxygen materials is D 50 Specifically, raw material D is sieved until it is 2 μm to 10 μm in size. 50 The value may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, but is not limited to the recited values, and other unrecited values within the numerical range are equally applicable.
[0311] In a specific embodiment, the sieving comprises at least one of crushing, ball milling, screening, and classifying.
[0312] In another embodiment of the method for producing a silicon-oxygen material, the primary particles of the silicon-oxygen material produced by adding an appropriate amount of reducing metal to the raw material for producing the silicon-oxygen material have a Wadell sphericity of more than 0.92, and the silicon oxide, reducing metal and / or reducing metal compound are uniformly distributed in the primary particles. The chemical formula of the silicon oxide is SiOx, and 0 <x<2である。
[0313] In the above-mentioned solution, a certain proportion of reducing metal is added to the raw material for producing the silicon-oxygen material, so that the reducing metal is heated and vaporized under the flow of plasma to form gaseous reducing metal vapor, thereby realizing doping into the silicon-oxygen material. The structure of the negative electrode material produced using the composite silicon-oxygen material as the raw material is stable, and the loss of active components caused by components such as air penetrating into the inside of the particles can be effectively avoided, and the structure and properties of the negative electrode material do not deteriorate during long-term storage, which is very suitable for lithium-ion batteries. Compared with simple silicon-oxygen materials, the reducing metal and / or reducing metal compound (especially lithium silicate) in the composite silicon-oxygen material can reduce the consumption of lithium escaped from the positive electrode material during the initial charging of the silicon-oxygen material, and the lithium-ion battery produced can greatly reduce the consumption of irreversible charging lithium, have a high charge-discharge specific capacity and excellent initial coulombic efficiency, and improve the cycle performance of the material.
[0314] In some embodiments, the reducible metal compound comprises at least one of a reducible metal oxide, a reducible metal silicide, and a reducible metal silicate.
[0315] In some embodiments, the reducible metal compound comprises a reducible metal silicate, and the reducible metal silicate is uniformly distributed within the primary particles.
[0316] In some embodiments, the silicate comprises lithium silicate, which has good lithium ion conductive properties, combines with a smaller crystal grain size, better ensures that lithium ions can smoothly complete the lithium absorption-release reaction, exhibits good multiplication performance, and is highly safe.
[0317] In some embodiments, the silicate is dispersed in the silicon oxide, which can alleviate the problem of volume expansion of silicon during charging and discharging; the primary particles with a spherical structure can further improve the structural stability of the material, and have excellent cycle performance and small volume effect, thereby providing excellent electrochemical performance.
[0318] In some embodiments, the reducing metal comprises at least one of an alkali metal, an alkaline earth metal, and a transition metal.
[0319] In some embodiments, the reducing metal is at least one selected from Li, K, Mg, Al, Ca, Zn, Na, and Ti.
[0320] In some embodiments, the reducing metal includes Li, and the molar ratio of Si to Li in the raw material for producing the silicon-oxygen material is (1 to 50):1, and may be specifically 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, or 50:1, etc., and is not limited thereto.
[0321] In some embodiments, step S220 includes: The reaction product is cooled to obtain silicon-oxygen materials including non-Li2Si2O5 silicates and silicon oxides.
[0322] In some embodiments, the reducing metal includes Mg, and the molar ratio of Si to Mg in the raw material for producing the silicon-oxygen material is (5 to 50):1, specifically, it may be 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, or 50:1, etc., but is not limited thereto.
[0323] Step S220 includes cooling the reaction product to obtain a silicon-oxygen material, which includes MgSiO3 silicate and silicon oxide.
[0324] In some embodiments, after step S220, the method further includes water washing and / or acid washing the heat-treated product.
[0325] In some embodiments, the acid used in the pickling comprises at least one of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, phosphoric acid, chromic acid, hydrofluoric acid, formic acid, and acetic acid.
[0326] In some embodiments, the acid used in the pickling comprises a mixture of nitric acid and hydrofluoric acid.
[0327] In some embodiments, the mass ratio of nitric acid to hydrofluoric acid is 1:(0.5 to 5), specifically, it may be 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4, or 1:5, etc., but is not limited thereto.
[0328] In some embodiments, the pickling time is from 10 minutes to 2000 minutes.
[0329] In some embodiments, after the heat-treated product is water-washed and / or acid-washed, the method further includes washing the washed product until neutral, and performing solid-liquid separation and drying.
[0330] In some embodiments, the method of solid-liquid separation includes at least one of centrifugation and filtration separation.
[0331] In some embodiments, the mode of drying comprises at least one of high temperature drying and freeze drying.
[0332] In another embodiment, a method for producing a silicon oxygen material includes the following steps. In step S310, the molten silicon oxide raw material is atomized to obtain an atomized product. In step S320, the atomized product is cooled to obtain a silicon oxygen material containing silicon oxide.
[0333] The chemical formula of the silicon oxide produced in this embodiment is SiOx (0 < x < 2). The silicon oxide is primary particles, and the Wadell sphericity of the silicon oxide is greater than 0.92.
[0334] In the above method, the molten silicon oxide raw material is atomized into silicon oxide droplets. The droplets automatically become spherical under the action of surface tension and harden into spherical silicon oxide after cooling. Since the spherical silicon oxide particles can maintain structural stability during the circulation process, the material has a low expansion rate and excellent cycle performance.
[0335] The present embodiment will be specifically described below.
[0336] Specifically, step S310 includes atomizing the raw material of the molten silicon oxygen material using pressurized gas.
[0337] In some embodiments, the pressurized gas is a protective gas.
[0338] Here, the protective gas includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0339] In some embodiments, the pressure of the pressurized gas is 0.2 Mpa to 100 Mpa. Specifically, the pressure may be 0.2 Mpa, 1 Mpa, 5 Mpa, 8 Mpa, 10 Mpa, 12 Mpa, 15 Mpa, 20 Mpa, 25 Mpa, 35 Mpa, 50 Mpa, 60 Mpa, 75 Mpa, 85 Mpa, or 100 Mpa, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0340] In some embodiments, before step S310, the method further includes heat treating the silicon oxide feedstock to a melt.
[0341] In some embodiments, the silicon oxide precursor is z, 0 <z<2である。
[0342] In some embodiments, the silicon oxide source includes at least one of SiO, a mixture of Si and SiO2, a mixture of Si and SiO2, and a mixture of SiO and SiO2.
[0343] In some embodiments, the temperature of the heat treatment is 1400° C. to 2200° C. Specifically, the temperature of the heat treatment may be 1400° C., 1500° C., 1600° C., 1800° C., 2000° C., or 2200° C.
[0344] In step S320, the atomized product is cooled to obtain a silicon-oxygen material containing silicon oxide.
[0345] In some embodiments, the step of cooling includes cooling to below 100° C. In particular, cooling to 90° C., 80° C., 75° C., 65° C., 60° C., 50° C., etc.
[0346] In some embodiments, the cooling rate is 1° C. / s to 100° C. / s. This cooling rate can rapidly cool the silicon oxide droplets, thereby obtaining a small Si crystallite size. Specifically, the cooling rate can be 1° C. / s, 10° C. / s, 20° C. / s, 35° C. / s, 45° C. / s, 60° C. / s, 70° C. / s, 80° C. / s, 90° C. / s, or 100° C. / s.
[0347] In some embodiments, the method of cooling employs gas cooling.
[0348] In some embodiments, the gas used for cooling is a protective gas.
[0349] Specifically, the protective gas contains at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0350] A method for manufacturing a negative electrode material according to another embodiment, which includes obtaining a composite material of a silicon-based material and a carbon material by adding an organic carbon source to a raw material for manufacturing silicon oxide, specifically includes the following steps. In step S410, the raw material containing silicon oxide and the organic carbon source is heat-treated to melt the organic carbon source. In step S420, the raw material containing silicon oxide and the molten organic carbon source is atomized. In step S430, the atomized product is cooled to obtain a spherical intermediate. In step S440, the spherical intermediate is carbonized to obtain a negative electrode material.
[0351] The negative electrode material manufactured by this method contains silicon oxide and a carbon material. The chemical formula of the silicon oxide is SiOx (0 < x < 2). The negative electrode material is spherical particles, and the Wadell sphericity of the negative electrode material is greater than 0.3.
[0352] In the above solution, the organic carbon source melts into a melt with high fluidity. The silicon oxide is still uniformly dispersed in the melt in a solid phase. The melt system is dispersed into atomized droplets using a pressurized gas. The solid silicon oxide is dispersed in the organic carbon source droplets. The droplets automatically contract into a spherical shape under the action of surface tension and eliminate the bubbles inside themselves to form a dense structure. After further cooling, it becomes a solid spherical intermediate. The spherical intermediate undergoes carbonization treatment, the carbon source is converted into an amorphous carbon material, and the silicon oxide is dispersed in the amorphous carbon material to form a spherical negative electrode material. The spherical negative electrode material still maintains the form of the spherical intermediate and has a high sphericity.
[0353] Specifically, SiO w is SiO 0.5 、SiO 1.0 、SiO 1.2 、SiO 1.5 or SiO1.8 etc.
[0354] In some embodiments, SiO w includes at least one of SiO, a mixture of Si and SiO, a mixture of Si and SiO2, and a mixture of SiO and SiO2.
[0355] In some embodiments, SiO w D 50 D 50 ≦1.5 μm.
[0356] In some embodiments, the silicon oxide source further comprises a molten organic carbon source.
[0357] In some embodiments, the organic carbon source comprises at least one of sugars, esters, hydrocarbons, organic acids, and high molecular weight polymers.
[0358] In some embodiments, the organic carbon source is polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, citric acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose. ,a The resin composition contains at least one of sphalt, furfural resin, epoxy resin, and phenolic resin.
[0359] In some embodiments, the temperature of the heat treatment is 100° C. to 600° C. In a specific example, the temperature of the heat treatment may be 100° C., 120° C., 150° C., 200° C., 250° C., 280° C., 300° C., 400° C., 450° C., 500° C., 550° C., or 600° C., etc. The melting point of the organic carbon source is much lower than that of silicon oxide, and the temperature of this heat treatment reaches the melting temperature of the organic carbon source, and the spherical negative electrode material can be produced without needing to be heated to the melting point of silicon oxide, and the increase in the Si crystallite size in the silicon oxide due to high temperature is avoided and kept within 50 nm.
[0360] Additionally, the feedstock further includes graphite, the addition of which helps increase the electrical conductivity and first coulombic efficiency of the system.
[0361] In some embodiments, when the total mass of graphite, SiOw, and the organic carbon source is 100%, the mass fraction of graphite is 0% to 40%, and SiO w The mass fraction of the organic carbon source is 40% to 95%, and the mass fraction of the organic carbon source is 5% to 60%.
[0362] In some embodiments, the graphite comprises at least one of natural graphite, synthetic graphite, and mesocarbon microbeads.
[0363] In step S420, the raw material including the silicon oxide and the molten organic carbon source is atomized using pressurized gas.
[0364] The product obtained by atomizing a feedstock containing silicon oxide and a molten organic carbon source has silicon oxide particles dispersed in organic carbon source droplets.
[0365] In some embodiments, the pressure of the pressurized gas is 0.2 MPa to 100 MPa, and the pressurized gas having a pressure in this range can atomize the raw material including the silicon oxide and the molten organic carbon source. In a specific example, the pressure of the pressurized gas may be 0.2 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa, 70 MPa, 80 MPa, 90 MPa, or 100 MPa.
[0366] In some embodiments, the pressurized gas comprises a protective gas, the protective gas comprising at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0367] The atomization method can use a general atomization device in this field, and the raw material containing silicon oxide and a molten organic carbon source is atomized to disperse silicon oxide particles in the organic carbon source droplets.
[0368] In step S430, the atomized product is cooled to obtain spherical intermediates.
[0369] In some embodiments, the cooling step involves cooling the atomized product to below 100°C.
[0370] In some embodiments, the cooling rate is from 1° C. / s to 100° C. / s, and rapid cooling helps to obtain a small Si crystallite size.
[0371] In some embodiments, the cooling process is gas cooling and further the gas is a protective gas.
[0372] Furthermore, the protective gas includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0373] In step S440, the spherical intermediate body is carbonized to obtain a negative electrode material.
[0374] In some embodiments, the carbonization process is carried out under a protective atmosphere.
[0375] Further, the gas of the protective atmosphere includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas.
[0376] In some embodiments, the carbonization temperature is 600° C. to 1000° C., and the carbonization time is 1 hour to 24 hours.
[0377] In some embodiments, the method further comprises adding a carbon source gas to the feedstock to produce the silicon oxygen material and performing a secondary granulation.
[0378] In a specific embodiment, a carbon source gas and a silicon oxygen material are transported into a plasma stream for secondary granulation, and then cooled to obtain a negative electrode material containing silicon oxide and a carbon material. Here, the negative electrode material is secondary particles, the chemical formula of the silicon oxide is SiOx (0 < x < 2), and the Wadell sphericity of the negative electrode material is greater than 0.91.
[0379] In the above solution, the sphericity of the product formed by secondary granulation of silicon oxide is high, which increases the stress of the internal structure, improves the strength of the material, and further improves the cycle and rate performance.
[0380] In some embodiments, the silicon oxygen material is primary particles of silicon oxide.
[0381] In some embodiments, among the silicon oxides, the volume of the powder with a particle size of 1.0 μm or less accounts for 15% or less of the total silicon oxides.
[0382] In some embodiments, the particle size of the silicon oxide is D 90 < 25.0 μm, D 10 > 0.5 μm, and satisfies 1 μm ≤ D 50 ≤ 10 μm.
[0383] In some embodiments, the Si crystallite size in the silicon oxide is 1.0 nm to 20 nm.
[0384] In some embodiments, the step of transporting the carbon source gas into the plasma stream for secondary granulation further includes adding a carbonaceous binder into the plasma stream.
[0385] In some embodiments, the carbonaceous binder includes at least one of saccharides, esters, hydrocarbons, organic acids, and polymer polymers.
[0386] In some embodiments, the carbonaceous adhesive comprises at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin.
[0387] In some embodiments, the mass ratio of the carbonaceous binder to the silicon oxide is from 5:95 to 50:50.
[0388] In some embodiments, the carbon source gas comprises hydrocarbons.
[0389] In some embodiments, the carbon source gas comprises at least one of methane, acetylene, ethylene, ethane, propane, propene, propyne, acetone, and benzene.
[0390] In some embodiments, the particle size D of the negative electrode material 50 is the grain size of silicon oxide D 50 It is 2 to 10 times that.
[0391] In some embodiments, the particle size of the negative electrode material is 20 μm≦D 90 ≦50μm, 5μm <D 50 <20μm and 2μm≦D 10 Meets ≦5μm.
[0392] In some embodiments, the mass content of carbon element in the negative electrode material is 2% to 20%.
[0393] In some embodiments, the porosity of the negative electrode material is between 1% and 50%.
[0394] In another embodiment, a method for producing a negative electrode material includes the following steps. In step S130, the silicon-oxygen material is subjected to a carbon coating process to obtain a negative electrode material. Here, the silicon oxygen material may be manufactured using steps S110 to S120.
[0395] The negative electrode material obtained by the manufacturing method includes a silicon oxygen material and a carbon layer coated on the surface of the silicon oxygen material. The silicon oxygen material contains silicon oxide, and the chemical formula of the silicon oxide is SiOx (0 < x < 2). The silicon oxygen material is a primary particle, and the Wadell sphericity of the silicon oxygen material is greater than 0.92.
[0396] In one embodiment, the carbon coating treatment is specifically at least one of solid-phase carbon coating, liquid-phase carbon coating, and gas-phase carbon coating.
[0397] Specifically, the gas-phase carbon coating is specifically to put the cooled product into a chemical vapor deposition apparatus, introduce a carbon source gas for pyrolysis, and deposit amorphous carbon on the material surface.
[0398] In some embodiments, the carbon source gas for gas-phase carbon coating contains hydrocarbons.
[0399] In some embodiments, the carbon source gas contains at least one of methane, acetylene, ethylene, ethane, propane, propene, propyne, acetone, and benzene.
[0400] In some embodiments, the chemical vapor deposition apparatus includes at least one of a rotary chemical vapor deposition reactor, a plasma-enhanced chemical vapor deposition reactor, a chemical vapor deposition tubular furnace, and a fluidized bed. Specifically, the chemical vapor deposition apparatus is at least one of a rotary furnace and a box-type furnace.
[0401] In some embodiments, the temperature of pyrolysis is 600°C to 1000°C.
[0402] In some embodiments, the heating temperature of the silicon oxygen material is 500°C to 1200°C, and the heat preservation time is 0.5 h to 20 h.
[0403] In some embodiments, the reaction pressure of the carbonization treatment is 1.0 atm to 10.0 atm.
[0404] In some embodiments, an auxiliary gas is further introduced when introducing the protective gas and the carbon source gas, the auxiliary gas comprises H2, and the molar ratio of the carbon source gas to the auxiliary gas is (2-10):1.
[0405] In some embodiments, the protective gas includes at least one of nitrogen gas, helium gas, neon gas, argon gas, krypton gas, and xenon gas.
[0406] In some embodiments, the solid-phase carbon coating process specifically includes mixing a silicon-oxygen material with a solid-phase carbon source, and then subjecting the mixture to a carbonization process to obtain a negative electrode material.
[0407] In some embodiments, the carbon source for the solid phase carbon coating includes at least one of sugars, esters, hydrocarbons, organic acids, and polymers, and may be at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin.
[0408] In some embodiments, the mixing manner of the cooled product with the carbon source may be VC mixing, fusion, ball milling, three-dimensional mixing, fluidized bed mixing, and the like.
[0409] In some embodiments, the mixing is performed in a blender, the blending time is 0.5 h to 2 h, and the rotation speed of the blender is 500 r / min to 5000 r / min.
[0410] In some embodiments, the mass ratio of the solid phase carbon source to the silicon oxygen material is 5:(5-95).
[0411] In some embodiments, the carbonization temperature is 500° C. to 1000° C., and the carbonization time is 2 hours to 20 hours.
[0412] In some embodiments, the solid state carbon coating equipment is at least one of a rotary kiln, a box kiln, a roller hearth kiln, a tunnel kiln, and a pusher kiln.
[0413] In some embodiments, the protective gas may be at least one of nitrogen gas, argon gas, helium gas, neon gas, krypton gas, and xenon gas.
[0414] Specifically, the liquid-phase carbon coating process involves uniformly mixing the cooled product with a carbon source, then placing the mixture in a furnace, introducing protective gas, and decomposing the carbon source through heat treatment to coat the surface of the cooled product.
[0415] In some embodiments, the carbon source for the liquid phase carbon coating is an organic carbon source, specifically, low temperature liquid phase asphalt, furfuryl alcohol, glycidyl methacrylate, triethylene glycol dimethacrylate, and the like.
[0416] In some embodiments, the protective gas may be at least one of nitrogen gas, argon gas, helium gas, neon gas, krypton gas, and xenon gas.
[0417] In some embodiments, the heat treatment temperature is between 600°C and 1000°C.
[0418] In another embodiment, the method for producing the anode material further includes, after producing the silicon-oxygen material: The silicon-oxygen material is coated with a coating solution containing a flexible polymer to obtain a negative electrode material.
[0419] In the above-mentioned solution, the present application uses a polymer coating solution to coat the silicon-oxygen material, and the polymer precipitates are coated on the surface of the silicon-oxygen material. The traction and binding action of the polymer helps maintain the electrical connection during the cycle expansion process of the silicon-oxygen material, and can effectively inhibit the expansion of the silicon-based active material, significantly improving the cycle expansion inhibition performance of the silicon-based active material, and prolonging the service life of the lithium-ion battery.
[0420] In some embodiments, the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer.
[0421] In some embodiments, the flexible polymer comprises at least one of polyolefins and their derivatives, polyvinyl alcohol and its derivatives, polyacrylic acid and its derivatives, polyamides and its derivatives, carboxymethylcellulose and its derivatives, and alginic acid and its derivatives.
[0422] In the present application, the term "natural flexible polymer and / or synthetic flexible polymer" refers to a natural flexible polymer, a synthetic flexible polymer, or a mixture of a natural flexible polymer and a synthetic flexible polymer.
[0423] Typical, but non-limiting examples of combinations of flexible polymers include combinations of polyolefins and polyvinyl alcohol, combinations of polyvinyl alcohol and carboxymethylcellulose, combinations of carboxymethylcellulose and alginic acid, combinations of polyamides and derivatives of carboxymethylcellulose, combinations of polyolefins, polyolefin derivatives and polyacrylic acid, combinations of polyvinyl alcohol, polyamide derivatives and alginic acid, combinations of polyolefins, polyvinyl alcohol, polyacrylic acid derivatives, polyamides and alginic acid, etc.
[0424] In some embodiments, the flexible polymer comprises polyolefins and their derivatives, and combinations of polyolefins and their derivatives, and alginic acid and its derivatives.
[0425] In some embodiments, the flexible polymer comprises polycarbonate.
[0426] In some embodiments, the weight average molecular weight of the flexible polymer is 2000 to 1000000, for example, 2000, 5000, 10000, 15000, 20000, 30000, 40000, 50000, 60000, 75000, 100000, 200000, 300000, 350000, 400000, 500000, 600000, 650000, 700000, 800000, 900000, or 1000000, etc., and is preferably 100000 to 500000.
[0427] In some embodiments, the flexible polymer comprises a thermal crosslinking functional group (also called a thermal crosslinkable functional group), and the thermal crosslinking functional group comprises at least one of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond. As can be understood, the thermal crosslinking functional group undergoes a crosslinking reaction under a condition of being heated to a certain temperature. As can be understood, crosslinking (also called a crosslinking reaction) is a relatively stable molecular (body-type molecular) reaction in which two or more molecules are bonded to each other and crosslinked into a network structure, and the crosslinking reaction can be divided into physical crosslinking, chemical crosslinking, etc. according to the triggering factor, and is not limited here.
[0428] In some embodiments, the coating liquid includes a solvent, and the solvent includes at least one of water, methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons.
[0429] In some embodiments, the coating solution comprises an antisolvent, the antisolvent comprising a poor solvent for the flexible polymer.
[0430] In some embodiments, the anti-solvent comprises at least one of methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons.
[0431] In some embodiments, the step of performing a coating process on the silicon-oxygen material using a coating solution containing the flexible polymer includes the following: A silicon-oxygen material is added to the flexible polymer coating liquid, and the mixture is stirred and separated to obtain a precursor of the negative electrode material, which is then subjected to a heat treatment.
[0432] In some embodiments, the temperature of the heat treatment is 100°C to 400°C, specifically, 100°C, 125°C, 150°C, 170°C, 200°C, 220°C, 240°C, 260°C, 300°C, 350°C, 400°C, etc., and is preferably 150°C to 250°C.
[0433] In some embodiments, the heat treatment time is 2 h to 12 h, and specifically may be 2 h, 4 h, 5 h, 6.5 h, 8 h, 10 h, 11 h, or 12 h, etc.
[0434] In some embodiments, the stirring temperature is 20°C to 100°C, and the stirring time is 1 to 24 hours. Specifically, the stirring temperature may be 20°C, 30°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, or 100°C, and the stirring time may be 1 hour, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 5 hours, 6 hours, 12 hours, 18 hours, or 24 hours.
[0435] In some embodiments, the coating liquid further comprises a conductive material.
[0436] In some embodiments, the conductive material includes flake graphite and nano-carbon based materials.
[0437] In some embodiments, flake graphite is attached to the surface of the silicon-oxygen material, a flexible polymer is coated on the surface of the silicon-oxygen material and the flake graphite, a nano-carbon material is filled in the area of the silicon-oxygen material that is not attached by the flake graphite, and / or a nano-carbon material is filled in the area of the silicon-oxygen material that is not covered by the flexible polymer. The flake graphite attached to the surface of the silicon-oxygen material, the flexible polymer and lithium silicate coated on the surface of the silicon-oxygen material and the flake graphite, and the nano-carbon material filled in the void area can effectively suppress the expansion of the silicon-oxygen material, and at the same time, the flake graphite is attached to the surface of the silicon-oxygen material and the void area is filled in the void area, so that the performance of the negative electrode material after coating is excellent, the cycle expansion performance is effectively suppressed, and the service life of the lithium-ion battery is extended.
[0438] In some embodiments, the scale graphite includes natural flake graphite and / or artificial flake graphite. In the present application, "natural flake graphite and / or artificial flake graphite" refers to natural flake graphite, artificial flake graphite, or a mixture of natural flake graphite and artificial flake graphite.
[0439] In some embodiments, the conductive material comprises a combination of flake graphite and nano-carbon-based material. When the conductive material is just a mixture of these two materials, the two materials can be blended with the silicon-based composite material to suppress the expansion of the silicon-based material, and further improve the electrical conductivity and electrical stability.
[0440] In some embodiments, the nano-carbon-based material comprises at least one of conductive graphite, graphene, carbon nanotubes, and carbon nanofibers.
[0441] In one possible embodiment, the conductive material may further include a conductive metal, a conductive alloy, etc. The conductive metal may be, for example, copper, aluminum, silver, gold, etc., and the conductive alloy may be, for example, a copper-zinc alloy, a copper-aluminum alloy, a titanium-zinc alloy, an aluminum-copper-zinc alloy, etc. As can be understood, when the conductive material includes these metal substances, these metal substances are also doped into the coating layer coated on the surface of the silicon-oxygen material, thereby further improving the electrical conductivity.
[0442] In some embodiments, the coating solution further comprises water-insoluble lithium silicate, which can effectively prevent the contact between the water in the electrolyte and the silicon-oxygen material, generate alkalinity, and even if the silicon-oxygen material is easily dissolved in water or shows strong alkalinity, it does not affect the water-based processing performance of the material.
[0443] In some embodiments, the water insoluble lithium silicate comprises at least one of Li2SiO3 and Li2Si2O5.
[0444] In some embodiments, the thickness of the coating layer is 10 nm to 5000 nm, and the thickness of the coating layer may be, for example, 10 nm, 20 nm, 30 nm, 50 nm, 60 nm, 70 nm, 80 nm, 100 nm, 200 nm, 300 nm, 500 nm, 1000 nm, or 5000 nm, etc., and is not limited thereto.
[0445] In some embodiments, the mass proportion of the coating layer in the negative electrode material is 0% to 20% (but not including 0%), for example, 0.5%, 1%, 3%, 3.5%, 5%, 6%, 8%, 10%, 12%, 13%, 15%, 16%, 18%, or 20%, and preferably 2% to 10%.
[0446] The present application further provides a lithium-ion battery, comprising the above-mentioned negative electrode material or a negative electrode material obtained by the method for producing the same.
[0447] A tab is provided, which comprises the negative electrode material described above or obtained by the manufacturing method described above.
[0448] The present application will be further described in the following by dividing it into several embodiments, but the present application is not limited to the following specific embodiments, and modifications can be appropriately made within the scope of protection.
[0449] Example 1 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator is controlled to be 8.5 kW, and the high frequency power is controlled to be 95 kW. Argon gas is used as the plasma generating gas. The flow rate of the direct current argon gas is 0.6 m / s. 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm is put into the plasma flow and reacted. Here, the flow rate of the carrier gas is 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water-cooling device and collected to obtain silicon-oxygen material.
[0450] The silicon-oxygen material of this embodiment is spherical SiO, and the spherical SiO is a primary particle.
[0451] Electron microscope photographs of the spherical SiO produced in this example are shown in Figures 2a and 2b. As can be seen from Figures 2a and 2b, the surface of the spherical SiO particles produced in this example is smooth, the sphericity of the spheres is good, and the cross-sectional view shows that the inside of the spheres also has a uniform structure.
[0452] Furthermore, (4) take SiO and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800 °C for 60 min, cool and remove the material, and obtain a negative electrode material in which SiO is coated with a carbon material.
[0453] The negative electrode material of this embodiment includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, and the spherical SiO is a primary particle. The maximum thickness of the carbon layer is 120 nm, the minimum thickness of the carbon layer is 80 nm, and the average particle diameter D of the negative electrode material is 1. 50 is 20 μm.
[0454] Example 2 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 100 kW, and the high frequency power was controlled to be 1000 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.2 m 3 / h, the pressure was 1000 torr, and the radial velocity of the plasma generating gas was 20 m 3 / h, and the tangential velocity is 5m 3 / h, the hot gas flow is restricted in the axial range, and a reducing atmosphere H2 is introduced, the radial velocity of which is 5 m 3 / h. (2) Mechanical milling was performed using nitrogen gas as a carrier gas. The powder was then crushed and classified using airflow. D 50 SiO and Si raw materials with a diameter of 5 μm were fed into the plasma jet flow, and the molar ratio of SiO to Si was 1:1. The carrier gas flow rate was 0.4 m 3 / h and the raw material supply rate is 60 g / min. (3) The product obtained in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and spherical SiO 0.5 The product is deposited on the wall of the water-cooling device and collected to obtain the silicon-oxygen material. (4)SiO 0.5The powder was placed in a CVD rotary furnace, methane was introduced as the carbon source, nitrogen gas was introduced as the protective gas, and the powder was deposited at 600 °C for 120 min. The powder was then cooled and the material was taken out. The carbon material was then converted to SiO 0.5 A negative electrode material is obtained that covers the above.
[0455] The silicon-oxygen material of this embodiment is spherical SiO 0.5 and spherical SiO 0.5 is the primary particle.
[0456] The spherical SiO 0.5 The electron microscope photograph of the above is shown in Figure 3. As can be seen from Figure 3, the surfaces of the spherical SiO particles produced in this example are smooth, and the sphericity of the spheres is good.
[0457] Furthermore, (4) SiO 0.5 The material was taken and placed in a CVD rotary furnace, methane was introduced as the carbon source, nitrogen gas was introduced as the protective gas, and deposition was performed at 600 °C for 120 min. The material was then cooled and removed, and the carbon material was converted to SiO 0.5 A negative electrode material is obtained that covers the above.
[0458] The negative electrode material in this embodiment is spherical SiO 0.5 and spherical SiO 0.5 The carbon layer is coated on the surface of the spherical SiO 0.5 is the primary particle. The maximum thickness of the carbon layer is 90 nm, the minimum thickness of the carbon layer is 70 nm, and the average particle size D 50 is 15 μm.
[0459] Example 3 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 200 kW, and the high frequency power was controlled to be 5000 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 2 m 3 / h, the pressure was 8000 torr, and the radial velocity of the plasma generating gas was 50 m 3 / h, and the tangential velocity is 10 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 SiO and SiO2 raw materials with a diameter of 5 μm are fed into the plasma jet flow and reacted. The molar ratio of SiO to SiO2 is 1:1, and the carrier gas flow rate is 1 m 3 / h and the raw material supply rate is 40 g / min. (3) The product obtained in step (2) is rapidly cooled by a water-cooling device at the tail of the plasma flow, and spherical SiO 1.5 The product is deposited on the wall of the water-cooling device and collected to obtain the silicon-oxygen material.
[0460] The silicon-oxygen material of this embodiment is spherical SiO 1.5 and spherical SiO 1.5 is the primary particle.
[0461] The spherical SiO 1.5 Electron micrographs of the spherical SiO 2 produced in this example are shown in Figures 4a and 4b. 1.5 The smoothness of the particle surface is not as good as that of Examples 1 and 2, the sphericity of the spheres is good, and the cross-sectional view shows that the inside of the spheres also has a uniform structure. Among them, the unevenness of the surface is found to be a structure in which Si and O are uniformly dispersed by EDS confirmation.
[0462] Furthermore, (4) SiO 1.5 The powder material was taken and placed in a CVD rotary furnace, ethylene was introduced as the carbon source, nitrogen gas was introduced as the protective gas, and deposition was performed at 1000°C for 30 min. The material was then cooled and taken out, and the carbon material was converted to SiO 1.5 A negative electrode material is obtained that covers the above.
[0463] The negative electrode material in this embodiment is spherical SiO 1.5 and spherical SiO 1.5 The carbon layer is coated on the surface of the spherical SiO 1.5is the primary particle. The maximum thickness of the carbon layer is 100 nm, the minimum thickness of the carbon layer is 75 nm, and the average particle size D of the negative electrode material is 50 is 12 μm.
[0464] Example 4 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 1000 kW, and the high frequency power was controlled to be 20000 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 1 m 3 / h, the pressure was 4000 torr, and the radial velocity of the plasma generating gas was 25 m 3 / h, and the tangential velocity is 8 m 3 / h, the hot gas flow is restricted in the axial range, a reducing atmosphere CH4 is introduced, and the radial velocity of the gas is 2 m 3 / h. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The Si and SiO2 raw materials with a diameter of 5 μm were fed into the plasma jet flow, and the molar ratio of Si to SiO2 was 1:1. The carrier gas flow rate was 0.5 m 3 / h and the raw material supply rate is 20 g / min. (3) The product obtained in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water-cooling device and collected to obtain silicon-oxygen material.
[0465] The silicon-oxygen material of this embodiment is spherical SiO, and the spherical SiO is a primary particle.
[0466] Electron micrographs of the spherical SiO produced in this example are shown in Figures 5a and 5b. As can be seen from Figures 5a and 5b, the spherical silicon oxide particles produced in this example have good sphericity, but a net-like structure appears on the surface, and heat generation during the chemical reaction may affect the surface properties. EDS confirmation shows that the spherical surface still has a uniform distribution of Si and O, and the net-like morphology does not affect the element distribution of the material.
[0467] Furthermore, (4) the SiO powder material is taken and put into a CVD rotary furnace, ethane is introduced as a carbon source, nitrogen gas is introduced as a protective gas, and the material is deposited at 1000°C for 90 min, cooled and discharged to obtain a carbon-coated SiO material.
[0468] The negative electrode material of this embodiment includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, and the spherical SiO is a primary particle. The maximum thickness of the carbon layer is 80 nm, the minimum thickness of the carbon layer is 50 nm, and the average particle diameter D of the negative electrode material is 1. 50 is 15 μm.
[0469] Example 5 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 2000 kW, and the high frequency power was controlled to be 50000 kW. Nitrogen gas was used as the plasma generating gas, and the flow rate of the direct current nitrogen gas was 0.5 m 3 / h, pressure was 2000 torr, and radial velocity was 80 m 3 / h, and the tangential velocity is 15 m 3 / h and the hot gas flow is restricted within the axial range. (2) Argon gas was used as a carrier gas, and SiH4 and O2 were used as raw materials in the plasma jet flow. The molar ratio of SiH4 to O2 was 2:3, and the flow rate of the carrier gas was 0.2 m 3 / h, and the flow rate of SiH4 is 2.5m 3 / h, and the O2 flow rate is 4m 3 / h. (3) The product obtained in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water-cooling device and collected to obtain silicon-oxygen material.
[0470] The silicon-oxygen material of this embodiment is spherical SiO, and the spherical SiO is a primary particle.
[0471] Furthermore, (4) the SiO powder material is taken and put into a CVD rotary furnace, propane is introduced as a carbon source, nitrogen gas is introduced as a protective gas, and deposition is performed at 900°C for 300 min, and then cooled and discharged to obtain a carbon-coated SiO material.
[0472] The negative electrode material of this embodiment includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, and the spherical SiO is a primary particle. The maximum thickness of the carbon layer is 150 nm, the minimum thickness of the carbon layer is 120 nm, and the average particle diameter D of the negative electrode material is 1. 50 is 8 μm.
[0473] Example 6 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 1 kg of SiO is placed in a melting crucible, heated to 1750°C, and kept at that temperature until it becomes molten. (2) The molten material is guided into the atomizing nozzle in the atomizing device, and the molten material is blown into small droplets using 2 MPa N2. At the same time, liquid nitrogen is introduced into the atomizing device and the temperature of the molten material is reduced to 50°C at a rate of 5°C / s, and the material is removed. (3) Collecting silicon oxygen material, the silicon oxygen material is spherical SiO, the spherical SiO is a primary particle. (4) The spherical powder is placed in a rotary furnace, and ethane gas is introduced to coat it at 1000°C to obtain the negative electrode material.
[0474] The negative electrode material includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, the spherical SiO is a primary particle, the mass content of oxygen element in the negative electrode material is 36.5%, the mass content of carbon element in the negative electrode material is 5.1%, the thickness of the carbon layer is 100 nm, and the D of the negative electrode material is 50 is 5 μm.
[0475] Example 7 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 1 kg of SiO is placed in a melting crucible, heated to 1750°C, and kept at that temperature until it becomes molten. (2) The molten material is guided into the atomization nozzle in the atomization device, and the molten material is blown into small droplets using N2 at 40 MPa. At the same time, liquid nitrogen is introduced into the atomization device and the temperature of the molten material is reduced to 50°C at a rate of 100°C / s, and the material is removed. (3) Collecting silicon oxygen material, the silicon oxygen material is spherical SiO, the spherical SiO is a primary particle. (4) The silicon-oxygen material is placed in a rotary furnace and preheated to 1000°C. Ethane gas is introduced to carry out a gas-phase carbon coating process at 1000°C. The reaction gas pressure for the carbon coating process is 5 atm.
[0476] The negative electrode material prepared in the examples of the present application includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, the spherical SiO is a primary particle, the mass content of oxygen element in the negative electrode material is 36.3%, and the mass content of carbon element in the negative electrode material is 4.7%.
[0477] Example 8 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 800 g of Si and 200 g of SiO are placed in a melting crucible, heated to 1600° C., and kept at that temperature until the mixture becomes molten. (2) The molten material is introduced into the atomizing nozzle in the atomizing device, and the molten material is blown into small droplets using 2 MPa N2. At the same time, liquid nitrogen is introduced into the atomizing device and the temperature of the molten material is reduced to 50°C at a rate of 20°C / s, and the material is removed. (3) Collecting silicon-oxygen material, which is spherical SiO 0.137 and spherical SiO 0.137 is the primary particle. (4) The silicon-oxygen material is placed in a rotary furnace, and ethane gas is introduced to carry out a vapor-phase carbon coating process at 1000°C. The reaction gas pressure for the carbon coating process is 8 atm.
[0478] The negative electrode material produced in this example is spherical SiO 0.137 and spherical SiO 0.137 Spherical SiO 0.137 is a primary particle, the mass content of oxygen element in the negative electrode material is 7.3%, the mass content of carbon element in the negative electrode material is 4.8%, and the specific surface area of the negative electrode material is 5 m 2 / g.
[0479] Example 9 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 800 g of SiO and 200 g of SiO2 are placed in a melting crucible, heated to 1750°C, and kept at that temperature until it becomes molten. (2) The molten material is introduced into the atomizing nozzle in the atomizing device, and the molten material is blown into small droplets using 2 MPa N2. At the same time, liquid nitrogen is introduced into the atomizing device and the temperature of the molten material is reduced to 50°C at a rate of 50°C / s, and the material is removed. (3) Collecting silicon-oxygen material, which is spherical SiO 1.155 and spherical SiO 1.155 is the primary particle. (4) The spherical powder is placed in a rotary furnace and ethane gas is introduced to coat it at 1000°C.
[0480] The negative electrode material in this embodiment is spherical SiO 1.155 and spherical SiO 1.155 The negative electrode material includes a carbon layer coated on the surface of the negative electrode material, the spherical SiO is a primary particle, the mass content of oxygen element in the negative electrode material is 39.9%, the mass content of carbon element in the negative electrode material is 4.8%, and the specific surface area of the negative electrode material is 6.7 m 2 / g.
[0481] Example 10 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 1 kg of SiO 0.5 The citric acid is melted by heat treating the above and 670 g of citric acid in argon gas at 200°C. (2)SiO 0.5 The molten citric acid is atomized into droplets using nitrogen gas at a pressure of 2 MPa. (3) The droplets are cooled to 50°C at a rate of 2°C / s under liquid nitrogen conditions to eject the material and obtain a spherical intermediate. (4) The spherical intermediate is carbonized at a carbonization temperature of 900°C for 12 hours, and the carbonization atmosphere gas is N2 to obtain a spherical negative electrode material.
[0482] The negative electrode material produced in this example was SiO 0.5 and amorphous carbon, the Wadell sphericity of the negative electrode material is 0.91, and SiO 0.5 is uniformly dispersed in the amorphous carbon, and SiO 0.5 accounts for 60% of the negative electrode material, and the porosity of the negative electrode material is 55.3%.
[0483] An electron microscope photograph of the negative electrode material prepared in this example is shown in Figure 6. As can be seen from Figure 6, the surface of the spherical negative electrode material prepared in this example is smooth, the sphericity of the sphere is good, and the cross-sectional view shows that the inside of the sphere also has a uniform structure.
[0484] Example 11 The method for producing the negative electrode material of this embodiment includes the following steps. (1) 1 kg of SiO 1.5 166 g of artificial graphite and 1.25 kg of glucose are heat-treated in nitrogen gas at 250° C. to melt the glucose. (2)SiO 1.5 The artificial graphite and molten glucose are dispersed as droplets using nitrogen gas with an air pressure of 40 MPa. (3) The droplets are cooled to 50°C at a rate of 5°C / s under liquid argon conditions to eject the material and obtain a spherical intermediate. (4) The spherical intermediate is carbonized at 900°C for 6 hours under N2 protective atmosphere to obtain a spherical negative electrode material.
[0485] The negative electrode material produced in this example was SiO 1.5 , artificial graphite and amorphous carbon, and the Wadell sphericity of the negative electrode material is 0.93. SiO 1.5 is uniformly dispersed in the amorphous carbon, the porosity of the negative electrode material is 50.5%, the artificial graphite accounts for 10% of the mass of the negative electrode material, and SiO 1.5 accounts for 50% of the mass of the negative electrode material.
[0486] Comparative Example 1 Take SiO and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800 °C for 60 min, cool and remove the material to obtain a negative electrode material in which SiO is coated with a carbon material.
[0487] The negative electrode material of this embodiment includes spherical SiO and a carbon layer coated on the surface of the spherical SiO, the spherical SiO is a primary particle, and the Wadell sphericity of the SiO powder material is 0.87. The maximum thickness of the carbon layer is 100 nm, the minimum thickness of the carbon layer is 80 nm, and the average particle diameter D of the negative electrode material is 0.87. 50 is 20 μm.
[0488] Performance Parameter Test The Mastersizer3000 uses laser diffraction technology to measure particle size. Particle size measurement is accomplished by measuring the intensity of scattered light when a laser beam passes through a dispersed particle sample. The data is then analyzed to calculate the particle size distribution of the particles forming a scattering spectrogram. 50 is the particle size when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that the particles with a particle size larger than this particle size account for 50% and the particles with a particle size smaller than this particle size account for 50%. D 50Also called the median diameter or median particle size. 90 Particle size, D 50 Particle size, D 10 The particle size is the equivalent diameter (average particle size) of the maximum particle when the cumulative distribution in the distribution curve is 90%, 50%, and 10%, respectively.
[0489] Using nitrogen gas adsorption multi-point BET, the specific surface area of powder samples is measured by gas adsorption at low temperatures controlled by liquid nitrogen cooling using a US Micro TriStar 3000 & 3020 specific surface area and pore size analyzer. The gas adsorption method (BET method) is also called the BET method because it is a multilayer adsorption theory (BET theory) method popularized by three people, including Brunauer, Emmett, and Teller, based on Langmuir's monolayer adsorption theory.
[0490] Measure XRD using a PANalytical X'pertPRO X-ray diffractometer in the scanning range of 9.749° to 41.157°. Scan step size: 0.013°, scan speed: 6.060° / min, voltage: 40 kV, current: 40 mA. Open the file in Jade6, perform background removal & smoothing, and then perform 26 o ~30 o The Si peaks in the range are fitted using the Scherrer equation D=kλ / βcosθ. D is the average grain size of the crystal grains perpendicular to the Si reflection crystal plane (111), and β (radius) is the degree of width at half maximum of the diffraction peak of the crystal plane = FWHM * π / 180. K is the Scherrer constant, which has a value of 0.89. θ is the diffraction angle, and λ is the incident X-ray wavelength, which has a value of 0.15406 nm. The full width at half maximum (FWHM) is abbreviated as FWHM. The full width at half maximum is also called the half width, half peak width, peak half width, region width, and region half width. It is a term in chromatographic analysis, and refers to the peak width at half the chromatographic peak height, i.e., a straight line is drawn through the midpoint of the peak height and parallel to the peak bottom, and the distance between this straight line and the two points that intersect on both sides of the peak. Here, FHWM and can both be obtained by XRD.
[0491] 1. Particle size distribution: D measured using a laser granulometer 50 , D 90 and D. 10 Measure and calculate (D 90 -D 10 ) / D 50 Get the value of .
[0492] 2. Specific surface area: The specific surface area is measured using a US Micro TriStar 3000 specific surface area and pore size analyzer.
[0493] 3. Wadell's sphericity test: Use a laser granulometer to measure the particle size distribution and obtain the equivalent volume diameter within each particle size range. The equivalent volume diameter is the particle size of all spheres within the very small particle size distribution range, and all particles within the range are equivalent to ideal spheres, and the specific surface area within each particle size distribution range is calculated, and then weighted by volume ratio% to obtain the specific surface area of a sphere with the same volume as all particles, so that the sphericity of the plasma-produced spherical particles = the surface area of a sphere with the same volume as the calculated particles / the specific surface area of the particles tested by the specific surface area meter.
[0494] 4. Si crystallite size: The Si crystallite size is obtained by measuring the XRD peaks using a PANalytical X'pert Pro X-ray diffractometer, and then fitting the Si peaks in the XRD using Jade 6.5 software.
[0495] 5.Electrical performance test: The composite material (materials of Examples 1 to 11), conductive carbon black, and PAA adhesive were mixed in a mass ratio of 75:15:10 to prepare an anode slurry, which was then applied onto copper foil and dried to produce an anode sheet. A metal lithium piece was used as the counter electrode, and the battery was assembled into a button battery in a glove box filled with argon gas for subsequent testing. A charge-discharge test was performed at a current density of 0.1 C in a charge-discharge range of 0.01 to 1.5 V. The initial reversible specific capacity and initial efficiency of the battery were obtained from the test.
[0496] Composite material (materials of Examples 1 to 11): Super-P:KS-6:CMC:SBR = 92:2:2:2:2 was prepared into an anode slurry, which was then applied onto copper foil and dried to produce an anode sheet. A metal lithium piece was used as the counter electrode, and the battery was assembled into a button battery in a glove box filled with argon gas for subsequent testing. A charge-discharge test was performed at a current density of 1C and a charge-discharge range of 0.01V to 1.5V. The volume expansion rate and capacity retention rate of the battery after 50 cycles were obtained by testing.
[0497] The test results of Examples 1 to 19 are shown in Table 1.
[0498] TIFF0007606198000001.tif116170
[0499] TIFF0007606198000002.tif169170
[0500] As can be seen from the test data of Examples 1 to 11, the silicon oxide is a primary particle of spherical silicon oxide with Wadell sphericity greater than 0.92. The spherical particles have isotropic characteristics, and uniformly contract and expand outward along the radial direction during the circulation process, and can maintain the stability of the structure under isotropic stress, and there is no "weak point" of stress due to the uneven shape. Therefore, the possibility of electrolyte penetrating into the material due to the collapse of the particle structure and the rupture of the SEI film is greatly reduced, and the electrolyte penetrating into the material and continuing to generate a new SEI film is effectively avoided, and the repeated fracture and generation of the SEI film is avoided, and the volume expansion of the material is reduced, and the cycle performance of the material is improved.
[0501] The Wadell sphericity of the SiO employed in Comparative Example 1 is only 0.87, and the sphericity of the material is poor and still has angularity, which leads to weak points of stress. At this time, the particle structure collapses and the SEI film ruptures, which increases the possibility of the electrolyte penetrating into the material, and local electrolyte penetration may occur. As a result, the SEI film thickness increase is higher than that of the sample with a Wadell sphericity of more than 0.92, and the capacity retention rate and expansion rate of the material are both deteriorated to a certain extent.
[0502] Example 12 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Mg are introduced into the plasma flow and reacted. The molar ratio of Si to Mg is 20:1. The carrier gas flow rate is 0.5 m. 3 / h and the raw material supply rate is 5g / min. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO and silicate product containing MgSiO obtained after cooling and solidification are attached to the wall of the water-cooling device to obtain a silicon-oxygen material.
[0503] The silicon oxygen material prepared in this embodiment is a spherical primary particle, the silicon oxygen material includes silicon oxide SiO and magnesium silicate, the mass content of oxygen element in the silicon oxygen material is 30%, the mass content of Mg element in the silicon oxygen material is 15%, and the mass content of silicate in the silicon oxygen material is 20%. As shown in Fig. 7a, in the element distribution diagram obtained by scanning the SEM cut surface of the primary particle of silicon oxygen material with X-ray, as shown in Fig. 7b, the Si element distribution surface is in a uniformly dispersed state, as shown in Fig. 7c, the O element distribution surface is in a uniformly dispersed state, and as shown in Fig. 7d, the Mg element distribution surface is in a uniformly dispersed state.
[0504] Furthermore, (4) take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0505] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on the surface of the silicon-oxygen material, and the carbon layer has a thickness of 50 nm.
[0506] Example 13 The method for producing the negative electrode material of this embodiment includes the following steps. (1) Take the SiO raw material and place it near the tail of the vacuum furnace. (2) Take 1 kg of dolomite and 500 g of silicon iron powder, put them into a VC mixer and mix for 30 minutes to obtain a mixture of 1.5 kg of dolomite and silicon iron powder. This mixture is put into the side close to the mouth of a vacuum furnace as a raw material for producing Mg. (3) The collector is placed in the collection chamber, heated to 1350℃ under negative pressure conditions with a vacuum degree of 3 Pa, and kept at that temperature for 24 hours. SiO vapor and Mg vapor are generated in the furnace, and the molar ratio of Si to Mg is 20:1. The homogeneously mixed gaseous mixture is rapidly condensed (condensation temperature is 900℃) to produce SiO-Mg material. After the reaction is completed, the device is cooled and the product is collected. (4) The collected product is pickled with nitric acid and hydrofluoric acid in a mass ratio of 1:1 for 1 hour, and the washed product is washed with deionized water until it becomes neutral. After filtering, it is dried at 100°C to obtain silicon-oxygen material.
[0507] The silicon oxygen material produced in this embodiment is a primary particle, and the silicon oxygen material includes silicon oxide SiO and magnesium silicate, and the mass content of oxygen element in the silicon oxygen material is 30%, the mass content of Mg element in the silicon oxygen material is 15%, and the mass content of silicate in the silicon oxygen material is 20%.
[0508] Furthermore, (5) take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0509] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on the surface of the silicon-oxygen material, and the carbon layer has a thickness of 50 nm.
[0510] TIFF0007606198000003.tif57170
[0511] TIFF0007606198000004.tif65170
[0512] As can be seen from the comparison between Examples 12 and 13, the negative electrode material includes a silicon-oxygen material and a carbon layer formed on the surface of the silicon-oxygen material, and the spherical particles of the silicon-oxygen material with improved sphericity have isotropic characteristics, so that they uniformly contract and expand outward along the radial direction during the cycling process, and are subjected to isotropic stress, so that the stability of the structure can be maintained. The highly spherical silicon-oxygen material and the carbon layer on the surface act synergistically to suppress side reactions between the negative electrode material and the electrolyte, thereby improving the conductivity and cycle stability of the negative electrode material, and further mitigating the volume expansion of the negative electrode material, thereby significantly improving its cycle performance.
[0513] Example 14 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 10 kW, and the high frequency power was controlled to be 200 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Mg are introduced into the plasma flow and reacted. The molar ratio of Si to Mg is 20:1. The carrier gas flow rate is 0.5 m. 3 / h and the raw material supply rate is 5g / min. (3) The product obtained by the reaction in step (2) is cooled by the water cooling device at the tail of the plasma flow, and the spherical SiO and silicate product containing MgSiO3 obtained after cooling and solidification are attached to the wall of the water cooling device to obtain silicon oxygen material. The silicon oxygen material produced in this embodiment is a spherical primary particle, and the silicon oxygen material contains silicon oxide SiO and magnesium silicate, and the mass content of oxygen element in the silicon oxygen material is 30%, the mass content of Mg element in the silicon oxygen material is 15%, and the mass content of silicate in the silicon oxygen material is 20%. Furthermore, (4) take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0514] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on the surface of the silicon-oxygen material, and the carbon layer has a thickness of 50 nm.
[0515] Example 15 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 20 kW, and the high frequency power was controlled to be 500 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Mg are introduced into the plasma flow and reacted. The molar ratio of Si to Mg is 20:1. The carrier gas flow rate is 0.5 m. 3 / h and the raw material supply rate is 5g / min. (3) The product obtained by the reaction in step (2) is cooled by the water cooling device at the tail of the plasma flow, and the spherical SiO and silicate product containing MgSiO3 obtained after cooling and solidification are attached to the wall of the water cooling device to obtain silicon oxygen material. The silicon oxygen material produced in this embodiment is a spherical primary particle, and the silicon oxygen material contains silicon oxide SiO and magnesium silicate, and the mass content of oxygen element in the silicon oxygen material is 30%, the mass content of Mg element in the silicon oxygen material is 15%, and the mass content of silicate in the silicon oxygen material is 20%. Furthermore, (4) take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as a carbon source and nitrogen gas as a protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0516] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on the surface of the silicon-oxygen material, and the carbon layer has a thickness of 50 nm.
[0517] TIFF0007606198000005.tif58170
[0518] TIFF0007606198000006.tif64170
[0519] As can be seen from the comparison between Examples 14 and 15, by adjusting the DC and RF power of the plasma, the Si crystal grain size in the final silicon-oxygen material is different, and the crystallization of the material with the Si crystal grain size being too large is significant, and it shows a large expansion rate during the circulation process, which makes it easy for particle crushing to occur, and reduces the cycle performance.
[0520] Example 16 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Li were reacted in the plasma flow. The flow rate of the carrier gas was 0.5 m. 3 / h, the raw material supply rate is 5 g / min, and the molar ratio of Si to Li in the raw material for producing the silicon-oxygen material is 20:1. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO obtained after cooling and solidifying, and the lithium silicate product containing Li2SiO3 and Li2Si2O5 are attached to the wall of the water-cooling device to obtain a silicon-oxygen material. The silicon-oxygen material is a primary particle, and the silicon-oxygen material contains SiO and lithium silicate, the lithium silicate contains Li2SiO3 and Li2Si2O5, and the lithium silicate is dispersed and distributed in SiO. (4) The product after the reaction is washed with water and pickled. The acid used in the pickling is a mixture of nitric acid and hydrofluoric acid, and the mass ratio of nitric acid to hydrofluoric acid is 1:2. The pickling time is 1000 min. The product is washed until it becomes neutral, and then centrifuged and dried at high temperature. (5) Take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as the carbon source and nitrogen gas as the protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0521] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on a core of the silicon-oxygen material, the mass content of carbon element in the negative electrode material is 10%, and the thickness of the carbon layer is 200 nm.
[0522] Example 17 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Li were reacted in the plasma flow, and the flow rate of the carrier gas was 0.5 m 3 / h, the raw material supply rate is 10 g / min, and the molar ratio of Si to Li in the raw material for producing the silicon-oxygen material is 1:2. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO obtained after cooling and solidifying, and the lithium silicate product containing Li2SiO3 and Li2Si2O5 are attached to the wall of the water-cooling device to obtain a silicon-oxygen material. The silicon-oxygen material is a primary particle, and the silicon-oxygen material contains SiO and lithium silicate, the lithium silicate contains Li2SiO3 and Li2Si2O5, and the lithium silicate is dispersed and distributed in SiO. (4) The product after the reaction is washed with water and pickled. The acid used in the pickling is a mixture of nitric acid and hydrofluoric acid, and the mass ratio of nitric acid to hydrofluoric acid is 1:2. The pickling time is 1000 min. The product is washed until it becomes neutral, and then centrifuged and dried at high temperature. (5) Take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as the carbon source and nitrogen gas as the protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0523] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on a core of the silicon-oxygen material, the mass content of carbon element in the negative electrode material is 10%, and the thickness of the carbon layer is 200 nm.
[0524] TIFF0007606198000007.tif57170
[0525] TIFF0007606198000008.tif64170
[0526] It can be seen from the comparison between Examples 16 and 17 that with an increase in the silicate content in the silicon-oxygen material, the reversible specific capacity of the anode material decreases and the initial efficiency improves; an increase in the silicate content generally leads to an increase in the Si crystal grains in the silicon-oxygen material, and the increased silicon crystal grains have a more significant volume expansion effect during the cycling process, so that the cycling performance of the anode material also deteriorates to a certain extent.
[0527] Example 18 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 10 kW, and the high frequency power was controlled to be 100 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Li were reacted in the plasma flow. The flow rate of the carrier gas was 0.5 m. 3 / h, the raw material supply rate is 5 g / min, and the molar ratio of Si to Li in the raw material for producing the silicon-oxygen material is 20:1. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO obtained after cooling and solidifying, and the lithium silicate product containing Li2SiO3 and Li2Si2O5 are attached to the wall of the water-cooling device to obtain a silicon-oxygen material. The silicon-oxygen material is a primary particle, and the silicon-oxygen material contains SiO and lithium silicate, the lithium silicate contains Li2SiO3 and Li2Si2O5, and the lithium silicate is dispersed and distributed in SiO. (4) The product after the reaction is washed with water and pickled. The acid used in the pickling is a mixture of nitric acid and hydrofluoric acid, and the mass ratio of nitric acid to hydrofluoric acid is 1:2. The pickling time is 1000 min. The product is washed until it becomes neutral, and then centrifuged and dried at high temperature. (5) Take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as the carbon source and nitrogen gas as the protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0528] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on a core of the silicon-oxygen material, the mass content of carbon element in the negative electrode material is 10%, and the thickness of the carbon layer is 200 nm.
[0529] Example 19 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 10 kW, and the high frequency power was controlled to be 100 kW. Argon gas was used as the plasma generating gas, and the flow rate of the direct current argon gas was 5 m 3 / h, the pressure was 20000 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Li are reacted in the plasma flow, and the flow rate of the carrier gas is 5 m 3 / h, the raw material supply rate is 5 g / min, and the molar ratio of Si to Li in the raw material for producing the silicon-oxygen material is 20:1. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO obtained after cooling and solidifying, and the lithium silicate product containing Li2SiO3 and Li2Si2O5 are attached to the wall of the water-cooling device to obtain a silicon-oxygen material. The silicon-oxygen material is a primary particle, and the silicon-oxygen material contains SiO and lithium silicate, the lithium silicate contains Li2SiO3 and Li2Si2O5, and the lithium silicate is distributed in SiO. (4) The product after the reaction is washed with water and pickled. The acid used in the pickling is a mixture of nitric acid and hydrofluoric acid, and the mass ratio of nitric acid to hydrofluoric acid is 1:2; the pickling time is 1000 min. The washed product is washed until it becomes neutral, and then centrifuged and dried at high temperature. (5) Take the silicon-oxygen material and place it in a CVD rotary furnace, introduce acetylene as the carbon source and nitrogen gas as the protective gas, deposit at 800°C for 60 minutes, cool and remove the material to obtain the negative electrode material.
[0530] The negative electrode material prepared in the present embodiment includes a silicon-oxygen material and a carbon layer coated on a core of the silicon-oxygen material, the mass content of carbon element in the negative electrode material is 10%, and the thickness of the carbon layer is 200 nm.
[0531] TIFF0007606198000009.tif52170
[0532] TIFF0007606198000010.tif64170
[0533] It can be seen from the comparison between Examples 18 and 19 that in Example 18, lithium silicate is dispersed and distributed in SiO, while in Example 19, the flow rate and pressure of the carrier gas are too high, so that the metal elements are not uniformly doped in the silicon-based material, and the lithium silicate also cannot be uniformly distributed in SiO, which causes the material to have stress weak points during charging and discharging, and reduces the electrochemical performance.
[0534] Example 20 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) After coating the obtained spherical SiO, 100g of SiO powder is placed in a rotary furnace, and nitrogen gas is introduced into the furnace to replace the atmosphere. When the oxygen content in the exhaust gas is less than 200ppm, the temperature is increased to 600°C at 2°C / min, acetylene gas is introduced, and the flow rate is 0.2L / min. N2 protective atmosphere is introduced during the entire reaction process, and the gas flow rate is controlled to 0.1L / min. The reaction gas pressure is maintained at 1atm. After the reaction is continued for 10h, the acetylene gas is cut off, and the temperature is naturally lowered to obtain a composite negative electrode material.
[0535] The negative electrode material prepared in this example includes a SiO core and a carbon layer coated on the SiO core, and the mass content of carbon in the negative electrode material is 2.85%. The silicon characteristic peak A in the Raman spectrum of the negative electrode material prepared in this example is 504 cm -1 The carbon characteristic peak D is at 1352 cm -1 The carbon characteristic peak G is at 1601 cm -1 The graphene characteristic peak B is at 2695 cm -1 and has a peak intensity I A = 90.6, and I D = 110, and I G = 106, and I B = 56.4, and I A / I B is 1.61, and I B / I D is 0.51, and I D / I G is 1.04.
[0536] Example 21 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) After coating the obtained spherical SiO, 100 g of SiO powder is placed in a rotary furnace, and nitrogen gas is introduced into the furnace to replace the atmosphere. When the oxygen content in the exhaust gas is less than 200 ppm, the temperature is increased to 600 °C at 2 °C / min, acetylene gas is introduced, and the flow rate is 0.5 L / min. N2 protective atmosphere is introduced during the entire reaction process, and the gas flow rate is controlled to 1 L / min. The reaction gas pressure is maintained at 2 atm. After the reaction is continued for 10 h, the acetylene gas is cut off, and the temperature is naturally lowered to obtain a composite negative electrode material.
[0537] The negative electrode material prepared in this example includes a SiO core and a carbon layer coated on the SiO core, and the mass content of carbon in the negative electrode material is 3.96%. The silicon characteristic peak A in the Raman spectrum of the negative electrode material prepared in this example is 504 cm -1 The carbon characteristic peak D is at 1352 cm -1 The carbon characteristic peak G is at 1601 cm -1 The graphene characteristic peak B is at 2695 cm -1and has a peak intensity I A = 90.6, and I D = 110, and I G = 106, and I B = 112.3, and I A / I B is 1.61, and I B / I D is 1.02, and I D / I G is 1.04.
[0538] Example 22 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) After coating the obtained spherical SiO, 100 g of SiO powder is placed in a rotary furnace, and nitrogen gas is introduced into the furnace to replace the atmosphere. When the oxygen content in the exhaust gas is less than 200 ppm, the temperature is increased to 900 °C at 2 °C / min, acetylene gas is introduced, and the flow rate is 0.5 L / min. N2 protective atmosphere is introduced during the entire reaction process, and the gas flow rate is controlled to 1 L / min. The reaction gas pressure is maintained at 2 atm. After the reaction is continued for 10 h, the acetylene gas is cut off, and the temperature is naturally lowered to obtain a composite negative electrode material.
[0539] The negative electrode material prepared in this example includes a SiO core and a carbon layer coated on the SiO core, and the mass content of carbon in the negative electrode material is 4.68%. The silicon characteristic peak A in the Raman spectrum of the negative electrode material prepared in this example is 504 cm -1 The carbon characteristic peak D is at 1352 cm -1 The carbon characteristic peak G is at 1601 cm -1 The graphene characteristic peak B is at 2695 cm -1 and has a peak intensity I A = 10.6, and I D = 110, and I G = 106, and I B = 112.3, and I A / I B is 0.09, and I B / I D is 1.02, and I D / I G is 1.04.
[0540] Example 23 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) After coating the obtained spherical SiO, 100 g of SiO powder is placed in a rotary furnace, and nitrogen gas is introduced into the furnace to replace the atmosphere. When the oxygen content in the exhaust gas is less than 200 ppm, the temperature is increased to 700 °C at 2 °C / min, acetylene gas is introduced, and the flow rate is 1 L / min. N2 protective atmosphere is introduced during the entire reaction process, and the gas flow rate is controlled to 1.5 L / min. The reaction gas pressure is maintained at 2 atm. After the reaction is continued for 10 h, the acetylene gas is cut off, and the temperature is naturally lowered to obtain a composite negative electrode material.
[0541] The negative electrode material prepared in this example includes a SiO core and a carbon layer coated on the SiO core, and the mass content of carbon in the negative electrode material is 4.38%. The silicon characteristic peak A in the Raman spectrum of the negative electrode material prepared in this example is 504 cm -1 The carbon characteristic peak D is at 1352 cm -1 The carbon characteristic peak G is at 1601 cm -1 The graphene characteristic peak B is at 2695 cm -1 and has a peak intensity I A = 10.6, and I D = 110, and I G = 50, and I B = 112.3, and I A / I B is 0.09, and I B / I D is 1.02, and I D / I G is 2.2.
[0542] TIFF0007606198000011.tif70170
[0543] TIFF0007606198000012.tif87170
[0544] As can be seen from the comparison of the test data of Examples 20 to 23, the carbon characteristic peak, silicon characteristic peak, and Graphene The characteristic peak needs to be controlled within a suitable range, so that the material can have excellent electrochemical performance. If the layered structure of graphene is too large, it will result in an increase in the specific surface area and an increase in the mass content of carbon element in the negative electrode material, which is disadvantageous to improving the initial reversible capacity and initial coulombic efficiency of the material.
[0545] Example 24 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) 5g of vinylene carbonate is dissolved in 100ml of ethyl acetate, heated to 50℃, added with 0.2g of ammonium persulfate, stirred and reacted for 1h, added with 100g of SiO, 0.2g of ammonium persulfate and 5g of water, reacted for 5h, cooled, filtered by suction to separate the solid material, placed in a drying box at 100℃ and heat-treated for 10h, cooled to obtain the negative electrode material.
[0546] The negative electrode material produced in this embodiment includes a silicon-oxygen material and a coating layer located on the surface of the silicon-oxygen material, the thickness of the coating layer is 500 nm, the mass ratio of the coating layer to the negative electrode material is 8%, and the coating layer is polycarbonate.
[0547] Example 25 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) 4g of polyacrylic acid is dissolved in 100ml of distilled water, heated to 40℃, stirred and reacted for 2h, added with 100g of SiO and 5g of water, reacted at 60℃ for 2h, cooled, filtered by suction to separate the solid material, placed in a drying box at 180℃ for 4h of heat treatment, cooled to obtain the negative electrode material.
[0548] The negative electrode material produced in this embodiment includes a silicon-oxygen material and a coating layer located on the surface of the silicon-oxygen material, the thickness of the coating layer is 500 nm, the mass ratio of the coating layer to the negative electrode material is 6.5%, and the coating layer is polyacrylic acid.
[0549] Example 26 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm and metallic Mg are introduced into the plasma flow and reacted. The molar ratio of Si to Mg is 20:1. The carrier gas flow rate is 0.5 m. 3 / h and the raw material supply rate is 5g / min. (3) The product obtained by the reaction in step (2) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO and silicate product containing MgSiO obtained after cooling and solidification are attached to the wall of the water-cooling device to obtain a silicon-oxygen material.
[0550] The silicon oxygen material produced in this embodiment is a spherical primary particle, the silicon oxygen material includes silicon oxide SiO and magnesium silicate, the mass content of oxygen element in the silicon oxygen material is 30%, the mass content of Mg element in the silicon oxygen material is 15%, and the mass content of silicate in the silicon oxygen material is 20%. In the element distribution map obtained by scanning the SEM cut surface of the primary particle of the silicon oxygen material with X-rays, the Si element distribution surface is in a uniformly dispersed state, the O element distribution surface is in a uniformly dispersed state, and the Mg element distribution surface is in a uniformly dispersed state.
[0551] In addition, (4) 5 g of vinylene carbonate is dissolved in 100 ml of ethyl acetate, heated to 50°C, added with 0.2 g of ammonium persulfate, stirred and reacted for 1 hour, added with 100 g of SiO, 0.2 g of ammonium persulfate and 5 g of water, reacted for 5 hours, cooled, filtered by suction to separate the solid material, placed in a drying box at 100°C for 10 hours of heat treatment, cooled to obtain the negative electrode material.
[0552] The negative electrode material produced in the examples of the present application includes a silicon-oxygen material and a coating layer coated on the surface of the silicon-oxygen material, the coating layer has a thickness of 500 nm, the mass ratio of the coating layer to the negative electrode material is 8%, and the coating layer is polycarbonate.
[0553] TIFF0007606198000013.tif65170
[0554] TIFF0007606198000014.tif75170
[0555] As can be seen from the comparison of Examples 24 and 25, different polymer coatings can be employed, both of which can contribute to improving the cycling performance of the material, but the mass content of the polymer in the negative electrode material affects the cycling performance of the material.
[0556] Example 27 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm was put into the plasma flow and reacted. The flow rate of the carrier gas was 0.5 m 3 / h and the raw material supply rate is 5 g / min. (3) The product obtained by the reaction in step (2) is cooled by a water cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water cooling device and collected to obtain a silicon-oxygen material. The silicon-oxygen material is spherical SiO, and the spherical SiO is a primary particle. (4) Dissolve 4g of vinylene carbonate in 100g of distilled water, and fully dissolve it at a temperature of 40℃. Add 1g of carbon nanofiber and 5g of flake graphite CSG-3 under stirring conditions. Stir for 2 hours, then add 200g of ethanol. Stir for 0.5 hours, and add 90g of spherical SiO with stirring. Stir at 60℃ for 2 hours, then cool to room temperature, filter by suction to separate the material, place in a drying box at 180℃ and heat treat for 4 hours. Cool and take out to obtain the negative electrode material.
[0557] The negative electrode material produced in this embodiment includes a silicon-oxygen material SiO and a coating layer located on the surface of the silicon-oxygen material SiO, the coating layer has a thickness of 300 nm, and the mass ratio of the coating layer to the negative electrode material is 5%, the coating layer includes polyacrylic acid, flake graphite and carbon nanofibers, the flake graphite is bonded to the surface of the silicon-oxygen material, and the polyacrylic acid coats the surfaces of the silicon-oxygen material and the flake graphite.
[0558] Example 28 The differences from Example 27 are as follows. (4) 4g of polyacrylic acid is dissolved in 100g of distilled water, and the mixture is fully dissolved at 40℃. Then, under stirring conditions, 1g of carbon nanofiber and 5g of flake graphite CSG-3 are added. After stirring for 2 hours, 200g of ethanol are added. Stirring is continued for 0.5 hours. Then, 90g of SiO is added thereto while stirring. After stirring for 2 hours at 60℃, the mixture is cooled to room temperature, and the material is separated by suction filtration. The mixture is placed in a drying box at 180℃ and heat-treated for 4 hours. After cooling, the mixture is taken out to obtain the negative electrode material.
[0559] The negative electrode material produced in this embodiment includes a silicon-oxygen material SiO and a coating layer located on the surface of the silicon-oxygen material SiO, the coating layer has a thickness of 300 nm, and the mass ratio of the coating layer to the negative electrode material is 5%, the coating layer includes polyacrylic acid, flake graphite and carbon nanofibers, the flake graphite is bonded to the surface of the silicon-oxygen material, and the polyacrylic acid coats the surfaces of the silicon-oxygen material and the flake graphite.
[0560] TIFF0007606198000015.tif58170
[0561] TIFF0007606198000016.tif65170
[0562] As can be seen from the comparison of Examples 27 and 28, the negative electrode material can be obtained through the polymer coating process, and the core silicon-oxygen material has higher sphericity, so that it can uniformly contract and expand outward along the radial direction during the cycling process, and can maintain the stability of the structure due to the isotropic stress, and the cycling performance of the negative electrode material is significantly improved.
[0563] Example 29 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm is put into the plasma flow and reacted, then cooled to obtain silicon oxide SiO. The carrier gas flow rate is 0.5 m 3 / h and the raw material supply rate is 5g / min. (3) Methane gas and polyacrylonitrile are introduced into a plasma generator using argon gas as a carrier gas to react with each other. The mass ratio of polyacrylonitrile to SiO is 1:4, the volume ratio of argon gas to methane gas is 10:2, and the carrier gas flow rate is 0.5 m 3 / h and the raw material supply rate is 5 g / min. (4) The product obtained by the reaction in step (3) is cooled by a water-cooling device at the tail of the plasma flow, and the spherical SiO product obtained after cooling and solidification is attached to the wall of the water-cooling device and collected to obtain the negative electrode material.
[0564] The negative electrode material of this embodiment is a spherical SiO-C composite material, the negative electrode material is a secondary particle, the negative electrode material includes a carbon material and silicon oxide distributed in the carbon material, the mass content of carbon element in the negative electrode material is 10%, the volume of the powder of silicon oxide having a particle size of 1.0 μm or less accounts for 9% of the total silicon oxide, and the particle size of the negative electrode material is D 90 is about 31 μm, and D 50 is about 20.3 μm, and D 10 is approximately 8.9 μm.
[0565] Example 30 The differences from Example 29 are as follows. In step (2), methane gas is introduced into the plasma generator and reacted.
[0566] The negative electrode material of this embodiment is a spherical SiO-C composite material, the negative electrode material is a secondary particle, the negative electrode material includes a carbon material and silicon oxide distributed in the carbon material, the mass content of carbon element in the negative electrode material is 5%, the volume of the powder of silicon oxide having a particle size of 1.0 μm or less accounts for 9% of the total silicon oxide, and the particle size of the negative electrode material is D 90 is about 36 μm, and D 50 is about 19 μm, and D 10 is approximately 11 μm.
[0567] TIFF0007606198000017.tif54170
[0568] TIFF0007606198000018.tif64170
[0569] As can be seen from the comparison of Examples 29 and 30, the higher the sphericity of the prepared negative electrode material, the more significantly the cycle performance of the negative electrode material is improved.
[0570] Example 31 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50The SiO raw material with a diameter of 5 μm is put into the plasma flow and reacted, then cooled to obtain silicon oxide SiO. The carrier gas flow rate is 1 m 3 / h and the raw material supply rate is 5g / min. (3) Argon gas is used as a carrier gas to generate plasma. acetylene Gas and polyacrylonitrile were introduced to react, the mass ratio of polyacrylonitrile to SiO was 1:4, the volume ratio of argon gas to acetylene gas was 10:2, and the flow rate of the carrier gas was 1 m 3 / h and the raw material supply rate is 5 g / min. (4) The product obtained by the reaction in step (3) is cooled in a water-cooling device at the tail of the plasma flow, and after cooling and solidifying, the product is adhered to the wall of the water-cooling device and collected to obtain the negative electrode material.
[0571] The negative electrode material of this embodiment is a spherical SiO-C composite material, the negative electrode material is a secondary particle, the negative electrode material includes a carbon material and silicon oxide distributed in the carbon material, the mass content of carbon element in the negative electrode material is 12%, the volume of the powder of silicon oxide having a particle size of 1.0 μm or less accounts for 8.5% of the total silicon oxide, and the particle size of the negative electrode material is D 90 is about 30 μm, and D 50 is about 15 μm, and D 10 is approximately 5 μm.
[0572] Example 32 The method for producing the negative electrode material of this embodiment includes the following steps. (1) The direct current power in the plasma generator was controlled to be 8.5 kW, and the high frequency power was controlled to be 95 kW. Argon gas was used as the plasma generating gas. The flow rate of the direct current argon gas was 0.6 m 3 / h, the pressure was 450 torr, and the radial velocity of the plasma generating gas was 8.4 m 3 / h, and the tangential velocity is 1.8 m 3 / h and the hot gas flow is restricted within the axial range. (2) Mechanical milling was performed using argon gas as the carrier gas. The powder was then crushed and classified using airflow. D 50 The SiO raw material with a diameter of 5 μm is put into the plasma flow and reacted, then cooled to obtain silicon oxide SiO. The carrier gas flow rate is 1 m 3 / h and the raw material supply rate is 5g / min. (3) Argon gas is used as a carrier gas to generate plasma. acetylene Gas and polyacrylonitrile were introduced to react, the mass ratio of polyacrylonitrile to SiO was 1:6, the volume ratio of argon gas to acetylene gas was 10:3, and the flow rate of the carrier gas was 1 m 3 / h and the raw material supply rate is 5 g / min. (4) The product obtained by the reaction in step (3) is cooled in a water-cooling device at the tail of the plasma flow, and after cooling and solidifying, the product is adhered to the wall of the water-cooling device and collected to obtain the negative electrode material.
[0573] The negative electrode material of this embodiment is a spherical SiO-C composite material, the negative electrode material is a secondary particle, the negative electrode material includes a carbon material and silicon oxide distributed in the carbon material, the mass content of carbon element in the negative electrode material is 10%, the volume of the powder of silicon oxide having a particle size of 1.0 μm or less accounts for 10% of the total silicon oxide, and the particle size of the negative electrode material is D 90 is about 55 μm, and D 50 is about 22 μm, and D 10 is approximately 11 μm.
[0574] TIFF0007606198000019.tif57170
[0575] TIFF0007606198000020.tif56170
[0576] As can be seen from the comparison of the test data of Examples 31 and 32, when the content of the carbonaceous binder and the carbon source gas is increased, the particle size of the negative electrode material increases significantly, thus causing excessive stress concentration of the particles during cycling, resulting in poor cycle performance.
[0577] In this application, the preferred embodiments are disclosed as above, but are not intended to limit the claims. Since a person skilled in the art can make some possible variations and modifications without departing from the concept of this application, the protection scope of this application should be based on the scope defined in the claims of this application.
Claims
1. 1. A silicon oxygen material, comprising: The silicon oxygen material is Silicon oxide, At least one of a reducing metal and a reducing metal compound Including, The chemical formula of the silicon oxide is SiOx (0<x<2), The silicon / oxygen material is a primary particle, the primary particle having a Wadell sphericity of greater than 0.92, and the silicon / oxygen material having a specific surface area of less than 10 m 2 / g.
2. The silicon-oxygen material is (1) The reducing metal includes at least one of an alkali metal, an alkaline earth metal, and a transition metal; (2) The reducing metal includes at least one of Li, K, Mg, Al, Ca, Zn, Na, and Ti; (3) the mass content of oxygen element in the silicon-oxygen material is 10% to 50%; (4) The mass content of the reducing metal element in the silicon-oxygen material is 0.5% to 50%; (5) In an element distribution diagram obtained by scanning an SEM cut surface of a primary particle of the silicon-oxygen material with an X-ray, the distribution surface of Si, O and reducing metal elements is in a uniformly dispersed state; (6) The reducible metal compound includes at least one of an oxide of a reducible metal, a silicide of a reducible metal, and a silicate of a reducible metal; (7) The reducing metal compound includes a reducing metal silicate, and the reducing metal silicate is uniformly distributed within the primary particles; and (8) The reducible metal compound includes a silicate of a reducible metal, and the mass content of the silicate in the silicon-oxygen material is 10% to 80%; (9) The reducing metal compound includes a reducing metal silicate, and the silicate includes lithium silicate; (10) The reducing metal compound includes a reducing metal silicate, the silicate includes lithium silicate, and the lithium silicate is Li 2 SiO 3 , Li 4 SiO 4 , Li 2 S 2 O 5 and Li 2 S 3 O 7 and (11) The reducing metal compound includes a reducing metal silicate, the silicate includes lithium silicate, and the lithium silicate is Li 2 S 2 O 5 And, (12) The reducing metal compound includes a reducing metal silicate, and the silicate is crystalline Li 2 S 2 O 5 Including Li 2 S 2 O 5 The grain size of the alloy is smaller than 20 nm; (13) The reducing metal compound includes a reducing metal silicate, and the silicate is crystalline Li 2 S 2 O 5 Li in the silicon oxygen material 2 S 2 O 5 The mass content of is 20% to 80%; (14) The reducing metal compound includes a reducing metal silicate, the silicate includes lithium silicate, and the molar ratio of Si to Li in the silicon-oxygen material is (1 to 50):1; 2. The silicon-oxygen material according to claim 1, which satisfies at least one of the following requirements:
3. (1) the Wadell sphericity of the primary particles is greater than 0.95; (2) The Si crystallite size in the silicon-oxygen material is 20 nm or less; (3) The Si crystallite size in the silicon-oxygen material is 10 nm or less; (4) D of the silicon-oxygen material 50 D 50 ≦50 μm; (5) The particle size distribution of the silicon-oxygen material is 3 μm<D 50 <10μm, 2μm≦D 10 ≦5 μm and 0.8≦(D 90 -D 10 ) / D 50 ≦1.2 is satisfied, (6) The silicon-oxygen material further comprises a nonmetallic doping element; 3. The silicon-oxygen material according to claim 1, which satisfies at least one of the above requirements.
4. A negative electrode material comprising the silicon-oxygen material of claim 1.
5. The negative electrode material is (1) The negative electrode material further comprises a carbon layer coated on a surface of the silicon-oxygen material; (2) the difference between the maximum and minimum thicknesses of the carbon layer is smaller than the minimum thickness; (3) the carbon layer has a thickness of 10 nm to 500 nm; (4) D of the negative electrode material 50 D 50 ≦100 μm; 5. The negative electrode material according to claim 4, which satisfies at least one of the following requirements.
6. The negative electrode material is (1) The negative electrode material further comprises a carbon material, the silicon oxygen material is dispersed in the carbon material, the negative electrode material is a spherical particle, and the Wadell sphericity of the negative electrode material is greater than 0.3; (2) the negative electrode material has a Wadell sphericity of greater than 0.5; (3) the negative electrode material has a Wadell sphericity of greater than 0.92; (4) In the silicon-oxygen material, the mass of oxygen element is 0% to 67% (but not including 0%) of the sum of the masses of silicon element and oxygen element; (5) D of the negative electrode material 50 D 50 ≦40 μm; (6) The porosity of the negative electrode material is less than 20%; and (7) the mass of the silicon-oxygen material accounts for 40% to 95% of the mass of the negative electrode material; (8) The negative electrode material further comprises a carbon material, the silicon oxygen material is dispersed in the carbon material, and the carbon material comprises amorphous carbon; (9) The negative electrode material further comprises graphite; (10) The negative electrode material further comprises graphite, the graphite comprising at least one of natural graphite, artificial graphite, and mesocarbon microbeads; (11) The negative electrode material further includes graphite, and when the total mass of the negative electrode material is 100%, the mass fraction of the graphite is 0% to 40%, the mass fraction of the silicon-oxygen material is 40% to 95%, and the mass fraction of the carbon material is 5% to 60%; (12) The negative electrode material further includes a carbon material, the carbon material is formed on a surface of the silicon-oxygen material, and the carbon material has a graphene structure; (13) In a Raman spectrum, the negative electrode material has a carbon characteristic peak D, a carbon characteristic peak G, a silicon characteristic peak A, and a graphene characteristic peak B; (14) Peak intensity I of the silicon characteristic peak A A and the peak intensity I of the graphene characteristic peak B B Comparison with I A / I B is 0.1 to 50, and the peak intensity I of the carbon characteristic peak D is D and the peak intensity I of the carbon characteristic peak G G Comparison with I D / I G is 0.5 to 2.0, and the peak intensity I B and the peak intensity I of the carbon characteristic peak D D Comparison with I B / I D is between 0 and 1, 5. The negative electrode material according to claim 4, which satisfies at least one of the following requirements.
7. 5. The negative electrode material of claim 4, further comprising a carbon material, the silicon-oxygen material being dispersed in the carbon material, the negative electrode material being a secondary particle, and the Wadell sphericity of the negative electrode material being greater than 0.
91.
8. The negative electrode material is (1) the silicon-oxygen material is a primary particle of silicon oxide; (2) the volume of the silicon oxide powder having a particle size of 1.0 μm or less accounts for 15% or less of the volume of the total silicon oxide; (3) The particle diameter of the silicon oxide is D 90 <25.0 μm, D 10 >0.5 μm and 1 μm≦D 50 ≦10 μm; (4) The silicon oxide has a Si crystallite size of 1.0 nm to 20 nm; (5) The specific surface area of the negative electrode material is 0.5 m 2 / g to 50m 2 / g, (6) The tap density of the negative electrode material is 0.5 g / cm 3 ~5.0g / cm 3 And, (7) Particle size D of the negative electrode material 50 is the particle diameter D of the silicon oxide 50 It is 2 to 10 times that (8) The particle size of the negative electrode material satisfies 20 μm≦D90≦50 μm, 5 μm<D50<20 μm, and 2 μm≦D10≦5 μm; (9) The mass content of carbon element in the negative electrode material is 2% to 20%; (10) The porosity of the negative electrode material is 1% to 50%; 8. The negative electrode material according to claim 7, which satisfies at least one of the following requirements.
9. 5. The anode material of claim 4, further comprising a coating layer located on a surface of the silicon-oxygen material, the coating layer comprising a flexible polymer.
10. The negative electrode material is (1) the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer; (2) The flexible polymer includes at least one of polyolefins and derivatives thereof, polyvinyl alcohol and derivatives thereof, polyacrylic acid and derivatives thereof, polyamides and derivatives thereof, carboxymethylcellulose and derivatives thereof, and alginic acid and derivatives thereof; (3) the weight average molecular weight of the flexible polymer is 2,000 to 1,000,000; (4) The flexible polymer includes a thermally crosslinkable functional group, and the thermally crosslinkable functional group includes at least one of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond; (5) The coating layer further includes a conductive material; (6) The conductive material includes flake graphite and a nanocarbon material; (7) The flake graphite includes natural flake graphite and / or artificial flake graphite; (8) The nanocarbon material includes at least one of conductive graphite, graphene, carbon nanotubes, and carbon nanofibers; (9) The coating layer further contains water-insoluble lithium silicate; (10) The water-insoluble lithium silicate is Li 2 SiO 3 and Li 2 S 2 O 5 and (11) The mass percentage of the flexible polymer is 0 to 10% (but not including 0) when the total mass of the silicon-oxygen material is 100%; (12) When the total mass of the silicon-oxygen material is 100%, the mass percentage of the flake graphite is 0 to 20% (but does not include 0); (13) When the total mass of the silicon-oxygen material is 100%, the mass percentage of the nanocarbon-based material is 0 to 5% (but does not include 0); (14) The flexible polymer comprises polycarbonate; and (15) The thickness of the coating layer is 10 nm to 5000 nm; (16) The mass ratio of the coating layer to the negative electrode material is 0% to 20% (but does not include 0%); (17) The mass ratio of the coating layer to the negative electrode material is 2% to 10%; and 10. The negative electrode material according to claim 9, which satisfies at least one of the following:
11. A method for producing the anode material of claim 4, comprising the steps of: The method includes the steps of: heat-treating a raw material for producing a silicon-oxygen material; and obtaining a silicon-oxygen material containing silicon oxide after cooling the raw material; The chemical formula of the silicon oxide is SiOx (0<x<2), and the Wadell sphericity of the silicon oxide material is greater than 0.92; The raw material is heat-treated to obtain a droplet-like product at high temperature, which then automatically becomes spherical due to the effect of surface tension during the cooling process, and hardens into the silicon-oxygen material with high sphericity; the raw material comprises at least one of Si, a mixture of SiOy and SiO2, a mixture of SiOy and Si, and a mixture of Si and SiO2, where 0<y<2; and / or The source material includes SiH 4 and O 2 , and The manufacturing method according to claim 1, wherein the raw material further contains a reducing metal.
12. The manufacturing method includes: (1) the step of heat treating the raw material for producing the silicon-oxygen material includes performing a plasma reaction on the raw material for producing the silicon-oxygen material; (2) the step of heat treating the raw material for producing the silicon-oxygen material includes transporting the raw material for producing the silicon-oxygen material into a plasma flow to perform a plasma reaction; (3) The step of heat treating the raw material for producing the silicon-oxygen material includes transporting the raw material for producing the silicon-oxygen material into a plasma flow to perform a plasma reaction, and the temperature in the plasma flow is 1400° C. to 2400° C.; (4) The step of heat treating the raw material for producing the silicon-oxygen material includes transporting the raw material for producing the silicon-oxygen material into a plasma flow to perform a plasma reaction, and the supply rate of the silicon oxide raw material is 2.0 g / min to 80 g / min; (5) The step of heat treating the raw material for producing the silicon-oxygen material includes carrying the raw material for producing silicon oxide into the plasma flow using a carrier gas to perform a plasma reaction; (6) The step of heat treating the raw material for producing the silicon-oxygen material includes carrying the raw material for producing silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas; (7) The step of heat treating the raw material for producing the silicon-oxygen material includes carrying the raw material for producing silicon oxide into the plasma flow using a carrier gas to perform a plasma reaction, and introducing a reducing gas, the reducing gas including at least one of methane and hydrogen gas; (8) The step of heat treating the raw material for producing the silicon-oxygen material includes carrying the raw material for producing silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas, and the molar ratio of the reducing gas to the silicon oxide is 0 to 0.25 (but does not include 0); (9) The step of heat treating the raw material for producing the silicon-oxygen material includes transporting the raw material for producing silicon oxide into the plasma flow using a carrier gas to carry out a plasma reaction, and introducing a reducing gas, and the radial velocity of the reducing gas is 1 m 3 / h~10m 3 / h, and (10) The reducing metal includes at least one of an alkali metal, an alkaline earth metal, and a transition metal; (11) The reducing metal includes at least one of Li, K, Mg, Al, Ca, Zn, Na, and Ti; (12) The reducing metal contains Li, and the molar ratio of Si to Li in the raw material for producing the silicon oxide is (1 to 50):1; (13) The reducing metal contains Mg, and the molar ratio of Si to Mg in the raw material for producing the silicon oxide is (5 to 50):1; (14) The method further comprises washing the product after the heat treatment with water and / or pickling, washing the washed product until it becomes neutral, and performing solid-liquid separation and drying; (15) The step of heat treating the raw material for producing the silicon and oxygen material includes atomizing the molten silicon and oxygen material raw material; (16) The step of heat treating the raw material for producing the silicon and oxygen material includes atomizing the molten silicon and oxygen material raw material by using a pressurized gas; (17) The step of heat treating the raw material for producing the silicon-oxygen material includes atomizing the molten silicon-oxygen material raw material using a pressurized gas, and the pressurized gas is a protective gas, and the protective gas includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas; (18) The step of heat treating the raw material for producing the silicon-oxygen material includes atomizing the molten silicon-oxygen material raw material using a pressurized gas, and the pressure of the pressurized gas is 0.2Mpa to 100Mpa; (19) The cooling step is to cool the silicon oxide raw material droplets to 100° C. or less; (20) The cooling rate is 1° C. / s to 100° C. / s; (21) The cooling is performed using a protective gas, and the protective gas includes at least one of nitrogen gas, argon gas, neon gas, krypton gas, and helium gas; 12. The method according to claim 11, wherein at least one of the following conditions is satisfied:
13. The manufacturing method includes: (1) The step of heat-treating the raw material for producing the silicon-oxygen material includes heat-treating the raw material containing the silicon-oxygen material and an organic carbon source to melt the organic carbon source, and performing an atomization process; (2) The step of heat-treating the raw material for producing the silicon-oxygen material includes heat-treating the raw material containing the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform atomization treatment, and the organic carbon source includes at least one of sugars, esters, hydrocarbons, organic acids, and polymers; (3) The step of heat treating the raw material for producing the silicon-oxygen material includes heat treating the raw material containing the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform atomization treatment, and the organic carbon source includes at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, citric acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, asphalt, furfural resin, epoxy resin and phenol resin; (4) The step of heat treating the raw material for producing the silicon-oxygen material includes heat treating the raw material containing the silicon-oxygen material and an organic carbon source to melt the organic carbon source and perform atomization treatment, and the mass ratio of the organic carbon source to the silicon oxide is 5: (5 to 95); (5) The step of heat treating the raw material for producing the silicon oxygen material includes heat treating the raw material containing the silicon oxygen material and the organic carbon source to melt the organic carbon source and perform atomization treatment, and the raw material containing the silicon oxygen material and the organic carbon source further contains graphite; (6) The method further includes carbonizing the cooled product to obtain a negative electrode material; (7) The method further includes carbonizing the cooled product to obtain a negative electrode material, and the temperature of the carbonization is 600° C. to 1000° C.; 12. The method according to claim 11, wherein at least one of the following conditions is satisfied:
14. 13. The method of claim 12, further comprising: conveying the carbon source gas and the silicon-oxygen material into a plasma flow to perform secondary granulation; and cooling to obtain an anode material comprising silicon oxide and a carbon material, wherein the anode material is a secondary particle, the chemical formula of the silicon oxide is SiOx (0<x<2), and the Wadell sphericity of the anode material is greater than 0.
91.
15. The manufacturing method includes: (1) the silicon-oxygen material is a primary particle of silicon oxide; (2) the volume of the silicon oxide powder having a particle size of 1.0 μm or less accounts for 15% or less of the volume of the total silicon oxide; (3) The particle diameter of the silicon oxide is D 90 <25.0 μm, D 10 >0.5 μm and 1 μm≦D 50 ≦10 μm; (4) The silicon oxide has a Si crystallite size of 1.0 nm to 20 nm; (5) The carbon source gas contains hydrocarbons; and (6) The carbon source gas includes at least one of methane, acetylene, ethylene, ethane, propane, propene, propyne, acetone, and benzene; (7) A volume ratio of the carrier gas to the carbon source gas is 10:(0.5 to 10); (8) The step of conveying the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous binder into the plasma flow; (9) The step of transporting the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous adhesive into the plasma flow, and the carbonaceous adhesive includes at least one of sugars, esters, hydrocarbons, organic acids, and polymers; (10) The step of transporting the carbon source gas and the silicon oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous adhesive into the plasma flow, and the carbonaceous adhesive includes at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin; (11) The step of transporting the carbon source gas and the silicon-oxygen material into the plasma flow to perform secondary granulation further includes adding a carbonaceous adhesive into the plasma flow, and the mass ratio of the carbonaceous adhesive to the silicon oxide is 5:95 to 50:50; (12) Particle size D of the negative electrode material 50 is the particle diameter D of the silicon oxide 50 It is 2 to 10 times that (13) The particle size of the negative electrode material is 20 μm≦D 90 ≦50μm, 5μm<D 50 <20 μm and 2 μm≦D 10 ≦5 μm; (14) The mass content of carbon element in the negative electrode material is 2% to 20%; (15) The porosity of the negative electrode material is 1% to 50%; (16) The specific surface area of the negative electrode material is 0.5 m 2 / g to 50m 2 / g, (17) The tap density of the negative electrode material is 0.5 g / cm 3 ~5.0g / cm 3 And, 15. The method according to claim 14, wherein at least one of the following conditions is satisfied:
16. The manufacturing method includes: (1) The method further includes performing a carbon coating process on the silicon-oxygen material to obtain a negative electrode material; (2) The manufacturing method further includes performing a carbon coating process on the silicon-oxygen material, the carbon coating process including at least one of solid-phase carbon coating, liquid-phase carbon coating, and gas-phase carbon coating; (3) The method further includes: heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and thermally decomposing the carbon source gas to obtain a negative electrode material; (4) The method further includes: heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and thermally decomposing the carbon source gas to obtain a negative electrode material, the carbon source gas being a hydrocarbon; (5) The method further includes: heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and thermally decomposing the carbon source gas to obtain a negative electrode material, wherein the carbon source gas includes at least one of methane, ethylene, acetylene, propyne, propene, propane, toluene, benzene, styrene, and phenol; (6) The method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material, and the temperature of the pyrolysis is 600° C. to 1000° C.; (7) The method further includes: heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and pyrolyzing the carbon source gas to obtain a negative electrode material; the heating temperature of the silicon-oxygen material is 500°C to 1200°C, and the heat retention time is 0.5h to 20h; (8) The method further includes: after heating the silicon-oxygen material, introducing a protective gas and a carbon source gas, and thermally decomposing the carbon source gas to obtain a negative electrode material; and the reaction gas pressure of the thermal decomposition is 1.0 atm to 10.0 atm; (9) The method further includes: after heating the silicon-oxygen material, introducing a protective gas, a carbon source gas and an auxiliary gas, and thermally decomposing the carbon source gas to obtain a negative electrode material; and the auxiliary gas is H 2 and (10) The method further includes: heating the silicon-oxygen material, introducing a protective gas, a carbon source gas and an auxiliary gas, and thermally decomposing the carbon source gas to obtain a negative electrode material; and the molar ratio of the carbon source gas to the auxiliary gas is (2-10):1; (11) The method further includes carbonizing the mixture obtained by mixing the silicon-oxygen material and a solid-phase carbon source to obtain a negative electrode material; (12) The method further includes carbonizing the mixture obtained by mixing the silicon-oxygen material and the solid-phase carbon source to obtain a negative electrode material, wherein the temperature of the carbonization is 500° C. to 1000° C., and the time of the carbonization is 2 h to 20 h; (13) The method further comprises: performing a carbonization process on the mixture obtained by mixing the silicon-oxygen material and a solid-phase carbon source to obtain a negative electrode material; and the solid-phase carbon source includes at least one of sugars, esters, hydrocarbons, organic acids, and polymers; (14) The method further comprises: mixing the silicon-oxygen material with a solid-phase carbon source to obtain a negative electrode material, and carbonizing the mixture; the solid-phase carbon source comprises at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin, and phenolic resin; (15) The method further includes carbonizing the mixture obtained by mixing the silicon-oxygen material and a solid-phase carbon source to obtain a negative electrode material, and the mass ratio of the solid-phase carbon source to the silicon-oxygen material is 5:(5 to 95); The manufacturing method according to any one of claims 11 to 13, characterized in that at least one of the following conditions is satisfied.
17. The manufacturing method according to any one of claims 11 to 13, further comprising: performing a coating process on the silicon-oxygen material using a coating solution containing a flexible polymer to obtain a negative electrode material.
18. The manufacturing method includes: (1) the flexible polymer comprises a natural flexible polymer and / or a synthetic flexible polymer; (2) The flexible polymer includes any one or a combination of at least two of polyolefins and derivatives thereof, polyvinyl alcohol and derivatives thereof, polyacrylic acid and derivatives thereof, polyamides and derivatives thereof, carboxymethylcellulose and derivatives thereof, and alginic acid and derivatives thereof; (3) the weight average molecular weight of the flexible polymer is 2,000 to 1,000,000; (4) The flexible polymer contains a thermally crosslinkable functional group, and the thermally crosslinkable functional group contains any one or a combination of at least two of an epoxy group, a carboxyl group, a hydroxyl group, an amino group, a double bond, and a triple bond; (5) The flexible polymer is a polyolefin or a derivative thereof, or a combination of a polyolefin or a derivative thereof and an alginic acid or a derivative thereof; (6) The coating liquid contains a solvent, and the solvent is any one or a combination of at least two selected from water, methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons; (7) The coating liquid includes an antisolvent, and the antisolvent is a poor solvent for the flexible polymer; (8) The coating liquid contains an antisolvent, and the antisolvent is any one or a combination of at least two selected from the group consisting of methanol, ethanol, polyvinylpyrrolidone, isopropanol, acetone, petroleum ether, tetrahydrofuran, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, normal hexane, and halogenated hydrocarbons; (9) The step of performing a coating treatment on the silicon-oxygen material using a coating liquid containing the flexible polymer includes adding a silicon-oxygen material to the coating liquid of the flexible polymer, stirring, and separating the material to obtain a negative electrode material precursor, and performing a heat treatment on the negative electrode material precursor; (10) The step of coating the silicon-oxygen material using the coating solution containing the flexible polymer includes adding the silicon-oxygen material to the coating solution of the flexible polymer, stirring, and separating to obtain a negative electrode material precursor, and subjecting the negative electrode material precursor to a heat treatment, the temperature of the heat treatment being 100° C. to 400° C., and the time of the heat treatment being 2 h to 12 h; (11) The step of coating the silicon-oxygen material using the coating solution containing the flexible polymer includes adding the silicon-oxygen material to the coating solution of the flexible polymer, stirring, and separating to obtain a negative electrode material precursor, and subjecting the negative electrode material precursor to a heat treatment, wherein the stirring temperature is 20° C. to 100° C., and the stirring time is 1 to 24 hours; (12) The coating liquid further contains a conductive material; (13) The coating liquid further contains a conductive material, and the conductive material contains flake graphite and a nanocarbon material; (14) The coating liquid further contains water-insoluble lithium silicate; (15) The coating liquid further contains a water-insoluble lithium silicate, and the water-insoluble lithium silicate is Li 2 SiO 3 and Li 2 S 2 O 5 and 18. The method according to claim 17, wherein at least one of the following conditions is satisfied:
19. A lithium ion battery comprising the silicon-oxygen material according to claim 1 or 2, or the negative electrode material according to any one of claims 4 to 10.
Citation Information
Patent Citations
Method for preparing SiOx composite anode material
CN105977463A
Silica fume based silicon monoxide negative electrode material, preparation method thereof and lithium ion battery
CN110357111A
Anode active material and preparation method and application thereof
CN111180693A
Nonaqueous secondary battery
JP2001118568A
Negative electrode material for nonaqueous electrolytic secondary batteries, method for manufacturing the same, and lithium ion secondary battery
JP2014225347A
